Crosslinked polymer particles for cosmetics or quasi-drugs

JP2025041410APending Publication Date: 2025-03-26NIPPON SHOKUBAI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023148688
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26

Smart Images

  • Figure 2025041410000001
    Figure 2025041410000001
  • Figure 2025041410000002
    Figure 2025041410000002
  • Figure 2025041410000003
    Figure 2025041410000003
Patent Text Reader

Abstract

To provide crosslinked polymer particles for cosmetics or quasi-drugs that can impart excellent thickness to the skin or hair when applied.SOLUTION: Provided is a crosslinked polymer particle for cosmetics or quasi-drugs, in which the content of structural units derived from (meth)acrylic acid (salt) per 100 pts.wt. of the crosslinked polymer is 20 pts.wt. or more and 100 pts.wt. or less, and the amount of residual monomer is 1000 ppm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to crosslinked polymer particles for use in cosmetics or quasi-drugs. [Background technology]

[0002] Conventionally, resin particles have been used in cosmetics or quasi-drugs for the purpose of improving the feeling of use when applied to the skin, etc. For example, a technology has been disclosed in which resin particles containing a crosslinked polymer having a specific monomer as an essential constituent unit are used for cosmetics (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2019-019058 Summary of the Invention [Problem to be solved by the invention]

[0004] However, conventional crosslinked polymer particles are not sufficient in terms of thickness when applied to the skin or hair, and there is room for improvement.

[0005] In view of the above circumstances, an object of one aspect of the present invention is to provide crosslinked polymer particles for cosmetics or quasi-drugs, which can impart excellent thickness when applied to skin or hair. [Means for solving the problem]

[0006] In order to solve the above problems, one aspect of the present invention includes the following configuration.

[0007] [1] A crosslinked polymer particle for use in a cosmetic preparation or a quasi-drug, the crosslinked polymer particle having a content of structural units derived from (meth)acrylic acid (salt) of 20 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the crosslinked polymer, and a residual monomer content of 1000 ppm or less.

[0008] [2] The crosslinked polymer particles for use in cosmetics or quasi-drugs according to [1], having a soluble content of 15% by mass or more.

[0009] [3] The crosslinked polymer particles for use in cosmetics or quasi-drugs according to [1], having a volume average particle size of 8 μm or more and 20 μm or less.

[0010] [4] The crosslinked polymer particles for cosmetics or quasi-drugs according to [1], wherein the crosslinked polymer is crosslinked with a compound having two or more ethylenically unsaturated groups in one molecule.

[0011] [5] The crosslinked polymer particles for use in cosmetics or quasi-drugs according to [1], wherein the content of structural units derived from a (meth)acrylate salt per 100 parts by mass of the crosslinked polymer is 20 parts by mass or more, and the (meth)acrylate salt is a salt of (meth)acrylic acid and a monovalent metal.

[0012] [6] A composition comprising the crosslinked polymer particles according to any one of [1] to [5] and an oil agent.

[0013] [7] A cosmetic or quasi-drug comprising the crosslinked polymer particles according to any one of [1] to [5] or the composition according to [6].

[0014] [8] The cosmetic or quasi-drug according to [7], which is for use on the skin. Effect of the Invention

[0015] According to one aspect of the present invention, it is possible to provide crosslinked polymer particles for cosmetics or quasi-drugs, which can impart excellent thickness when applied to skin or hair. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments or examples obtained by combining the technical means disclosed in different embodiments or examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".

[0017] [Crosslinked polymer particles] The crosslinked polymer particles according to one embodiment of the present invention (hereinafter, may be referred to as "the present crosslinked polymer particles") are crosslinked polymer particles for use in cosmetics or quasi-drugs, in which the structural unit derived from (meth)acrylic acid (salt) is 20 parts by mass or more and 100 parts by mass or less in 100 parts by mass of the crosslinked polymer, and the amount of residual monomer is 1000 ppm or less.

[0018] Since the present crosslinked polymer particles have the above-mentioned constitution, they can impart excellent thickness when applied to skin or hair. The "thickness" of the crosslinked polymer particles can be evaluated by the method described in the Examples.

[0019] In this specification, "acid (salt)" means "acid and / or its salt," and "(meth)acrylic" means "acrylic and / or methacrylic." In other words, "(meth)acrylic acid (salt)" means "acrylic acid (salt) and / or methacrylic acid (salt)."

[0020] In this specification, the term "resin" refers to a broader concept than polymer. A resin may contain one or more polymers, and may further contain materials other than polymers, such as monomers and additives, as necessary.

[0021] In this specification, the term "crosslinked polymer particles" refers to particles mainly composed of a crosslinked polymer. The crosslinked polymer particles may be composed of one or more types of crosslinked polymers. The crosslinked polymer particles may further contain, in addition to the crosslinked polymer, materials other than the crosslinked polymer, such as monomers and additives, as necessary.

[0022] ((Meth)acrylic acid (salt)) The present crosslinked polymer particles are crosslinked polymer particles containing structural units derived from (meth)acrylic acid (salt). In other words, the present crosslinked polymer particles are crosslinked polymer particles containing a crosslinked polymer obtained by polymerizing (and crosslinking) a monomer composition containing (meth)acrylic acid (salt). In this specification, the "structural unit derived from (meth)acrylic acid (salt)" refers to a repeating unit having a structure derived from (meth)acrylic acid (salt) among the repeating units contained in the polymer. Therefore, the present crosslinked polymer particles are preferably crosslinked polymer particles obtained by crosslinking a polymer obtained by polymerizing a monomer composition containing (meth)acrylic acid (salt).

[0023] Examples of the (meth)acrylic acid (salt) according to one embodiment of the present invention include acrylic acid (salt) and methacrylic acid (salt), and acrylic acid (salt) is more preferable.

[0024] The (meth)acrylic acid according to one embodiment of the present invention is not particularly limited in origin, and any known (meth)acrylic acid can be used. For example, the (meth)acrylic acid according to one embodiment of the present invention can be obtained by collecting gaseous (meth)acrylic acid obtained by catalytic gas phase oxidation with a solvent such as water, and then purifying the same by distillation, crystallization, or the like. The (meth)acrylic acid may contain trace amounts of components such as polymerization inhibitors and impurities.

[0025] In the present crosslinked polymer particles, the content of structural units derived from (meth)acrylic acid (salt) per 100 parts by mass of the crosslinked polymer is 20 parts by mass or more, preferably 30 parts by mass or more, more preferably 50 parts by mass or more, may be 70 parts by mass or more, or may be 90 parts by mass or more, may be 95 parts by mass or more, and is particularly preferably 100 parts by mass.

[0026] As the (meth)acrylic acid salt according to one embodiment of the present invention, for example, a salt obtained by neutralizing the above-mentioned (meth)acrylic acid with the following basic compound can be used.

[0027] The content of the structural unit derived from (meth)acrylate per 100 parts by mass of the crosslinked polymer contained in the present crosslinked polymer particle is preferably 20 parts by mass or more, more preferably 25 parts by mass or more, and even more preferably 30 parts by mass or more. In addition, the upper limit of the content of the structural unit derived from (meth)acrylate is not particularly limited, but is preferably 95 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 85 parts by mass or less.

[0028] (Basic compounds) In one embodiment of the present invention, the "basic compound" used for neutralizing (meth)acrylic acid specifically includes alkali metal carbonates, alkali metal hydrogen carbonates, alkali metal hydroxides, ammonia, organic amines, etc. From the viewpoint of the physical properties of the resulting crosslinked polymer particles, the basic compound is preferably a compound exhibiting strong basicity, and particularly preferably a monovalent or polyvalent metal salt. From the viewpoint of further improving the spread of the blend of crosslinked polymer particles when applied, among metal salts, monovalent metal salts are particularly preferred. That is, the present crosslinked polymer particles preferably contain a structural unit derived from a (meth)acrylic acid salt, which is a salt of (meth)acrylic acid and a monovalent metal. As such a monovalent metal salt, for example, a hydroxide of an alkali metal such as sodium, potassium, or lithium, more preferably sodium hydroxide, can be preferably exemplified.

[0029] From the above viewpoint, the content of the structural unit derived from the (meth)acrylic acid salt, which is a salt of (meth)acrylic acid and a monovalent metal, per 100 parts by mass of the crosslinked polymer contained in the present crosslinked polymer particle is preferably 20 parts by mass or more, more preferably 25 parts by mass or more, and even more preferably 30 parts by mass or more. In addition, the upper limit of the content of the structural unit derived from the (meth)acrylic acid salt is not particularly limited, but is preferably 95 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 85 parts by mass or less.

[0030] From the above viewpoint, the content of monovalent metal in the present crosslinked polymer particles per 100 moles of structural units derived from (meth)acrylic acid (salt) is preferably 20 moles or more and 100 moles or less, more preferably 40 moles or more and 100 moles or less, even more preferably 50 moles or more and 90 moles or less, and even more preferably 60 moles or more and 80 moles or less.

[0031] The content of polyvalent metal in the present crosslinked polymer particles relative to 100 moles of structural units derived from (meth)acrylic acid is not particularly limited, but from the viewpoint of good spreadability when applying a cosmetic containing the present crosslinked polymer particles, it is preferably 0.07 moles or less, more preferably 0.06 moles or less, even more preferably 0.05 moles or less, may be 0.01 moles or less, or may be 0 moles. In other words, the present crosslinked polymer particles may be substantially free of polyvalent metal.

[0032] The molar ratio of the monovalent metal to the polyvalent metal (moles of monovalent metal / moles of polyvalent metal) contained in the present crosslinked polymer particles is not particularly limited, but from the viewpoint of good spreadability when applying a cosmetic preparation containing the present crosslinked polymer particles, it is preferably 99.950 / 0.050 to 100 / 0, more preferably 99.990 / 0.010 to 100 / 0, and even more preferably 99.999 / 0.001 to 100 / 0.

[0033] (neutralization) The neutralization rate of (meth)acrylic acid, which is the raw material of the present crosslinked polymer particles, is not particularly limited, but is suitably set within the range of preferably 10 mol% to 90 mol%, more preferably 40 mol% to 85 mol%, further preferably 50 mol% to 80 mol%, and particularly preferably 60 mol% to 80 mol% with respect to the acid group of the monomer. By setting the neutralization rate of (meth)acrylic acid to 10 mol%, crosslinked polymer particles with excellent thickening properties can be provided. On the other hand, by setting the neutralization rate of (meth)acrylic acid to 90 mol% or less, the pH of the crosslinked polymer particles can be prevented from becoming excessively high. In addition, when a monomer having an acid group other than (meth)acrylic acid is used as the raw material of the crosslinked polymer, the neutralization rate is applied as the average neutralization rate of the entire monomer containing an acid group, including (meth)acrylic acid and a monomer having an acid group other than (meth)acrylic acid.

[0034] The crosslinked polymer particles may contain structural units derived from monomers other than (meth)acrylic acid (salt). In other words, the crosslinked polymer particles may be crosslinked polymer particles mainly composed of a crosslinked polymer containing (meth)acrylic acid (salt) and a monomer other than (meth)acrylic acid (salt), or may be crosslinked polymer particles mainly composed of a crosslinked polymer obtained by polymerizing (and crosslinking) a monomer composition containing (meth)acrylic acid (salt) and a monomer other than (meth)acrylic acid (salt). As the monomer other than (meth)acrylic acid (salt) that may be contained in the crosslinked polymer particles, a water-soluble monofunctional unsaturated monomer other than (meth)acrylic acid (salt) is preferred, and for example, a monofunctional unsaturated monomer having a carboxyl group other than (meth)acrylic acid (salt) is preferred.

[0035] In this specification, the term "monofunctional unsaturated monomer" specifically means a compound having one ethylenically unsaturated group in one molecule.

[0036] More specifically, examples of monomers other than (meth)acrylic acid (salts) from which the present crosslinked polymer particles can be derived include (anhydride) maleic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, 2-hydroxyethyl (meth)acryloyl phosphate, etc. Examples of the unsaturated monomers include anionic unsaturated monomers and their salts; mercaptan group-containing unsaturated monomers; phenolic hydroxyl group-containing unsaturated monomers; amide group-containing unsaturated monomers such as (meth)acrylamide, N-ethyl(meth)acrylamide, and N,N-dimethyl(meth)acrylamide; and amino group-containing unsaturated monomers such as N,N-dimethylaminoethyl(meth)acrylate, N,N-dimethylaminopropyl(meth)acrylate, and N,N-dimethylaminopropyl(meth)acrylamide. Among these, (meth)acrylamide is preferred. When the crosslinked polymer particles contain structural units derived from monomers other than (meth)acrylic acid (salt), the content ratio of structural units derived from monomers other than ((meth)acrylic acid (salt) per 100 parts by mass of the crosslinked polymer is preferably 50 to 80 parts by mass or more.

[0037] The crosslinked polymer as the main component of the present crosslinked polymer particle is not particularly limited in the crosslinking method, etc., as long as it is a polymer that is at least partially crosslinked, but it is preferably crosslinked using a crosslinking agent.In addition, the crosslinked polymer as the main component of the present crosslinked polymer particle is preferably crosslinked inside the crosslinked polymer, and may have a crosslinked structure on the surface of the crosslinked polymer, in other words, on the particle surface of the crosslinked polymer particle.

[0038] As the crosslinking agent used for crosslinking the crosslinked polymer, which is the main component of the crosslinked polymer particles, an internal crosslinking agent for crosslinking the inside of the crosslinked polymer, or a surface crosslinking agent for crosslinking the surface of the crosslinked polymer, etc., can be used according to the purpose. In addition, when crosslinking the crosslinked polymer, which is the main component of the crosslinked polymer particles, only one of the internal crosslinking agent or the surface crosslinking agent may be used as the crosslinking agent (in other words, only one of the inside or the particle surface of the crosslinked polymer particles may be crosslinked), or both the internal crosslinking agent and the surface crosslinking agent may be used (in other words, both the inside and the particle surface of the crosslinked polymer particles may be crosslinked). In this specification, "used for crosslinking the crosslinked polymer" refers to an operation of crosslinking an uncrosslinked polymer, which is a precursor of the crosslinked polymer (introducing a crosslinked structure), or an operation of further crosslinking a partially crosslinked polymer (for example, further crosslinking the surface of a crosslinked polymer only crosslinked inside).

[0039] Examples of crosslinking agents that can be used as internal crosslinking agents in the crosslinking of the crosslinked polymer that is the main component of the present crosslinked polymer particles include compounds having two or more ethylenically unsaturated groups in one molecule, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, N,N'-methylenebis(meth)acrylamide, triallyl isocyanurate, trimethylolpropane di(meth)allyl ether, triallylamine, tetraallyloxyethane, and glycerolpropoxy triacrylate; polyhydric alcohols such as choline, diethylene glycol, triethylene glycol, polyethylene glycol, glycerin, polyglycerin, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl alcohol, diethanolamine, tridiethanolamine, polypropylene glycol, polyvinyl alcohol, pentaerythritol, sorbitol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, 1,3-butanediol, 1,3-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,5-hexanediol, trimethylolpropane, sorbitol, sorbitan, glucose, mannitol, mannitan, sucrose, and glucose; polyglycidyl ethers such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, and glycerin triglycidyl ether;Polyamine compounds such as diethanolamine, triethanolamine, ethylenediamine, diethylenetriamine, and triethylenetetramine; polyglycidyl compounds such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, propylene glycol diglycidyl ether, and polypropylene glycol diglycidyl ether; 2,4-tolylene diisocyanate, ethylene carbonate (1,3-dioxolane- 2-one), propylene carbonate (4-methyl-1,3-dioxolan-2-one), 4,5-dimethyl-1,3-dioxolan-2-one, (poly, di, or mono) 2-oxazolidinone, epichlorohydrin, epibromohydrin, diglycol silicate, polyhydric aziridine compounds such as 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate], haloepoxy compounds such as epichlorohydrin and α-methylchlorohydrin; polyaldehydes such as glutaraldehyde and glyoxal; polyamines such as ethylenediamine;Examples of the internal crosslinking agent include hydroxides, halides, carbonates, oxides, and borates such as borax of metals in Groups 2A, 3B, and 8 of the periodic table, such as calcium hydroxide, calcium chloride, calcium carbonate, calcium oxide, magnesium chloride borax, magnesium oxide, aluminum chloride, zinc chloride, and nickel chloride, and polyvalent metal compounds such as aluminum isopropylate. As the internal crosslinking agent, a compound having two or more ethylenically unsaturated groups in one molecule is more preferable, and a compound having two or more ethylenically unsaturated groups in one molecule, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol di(meth)acrylate, is even more preferable. In other words, the crosslinked polymer, which is the main component of the crosslinked polymer particles, is preferably (internally) crosslinked with a compound having two or more ethylenically unsaturated groups in one molecule. By crosslinking the crosslinked polymer with a compound having two or more ethylenically unsaturated groups in one molecule, the entire crosslinked polymer can be uniformly crosslinked, and crosslinked polymer particles having excellent gel strength can be provided. As a result, a formulation containing the crosslinked polymer particles can impart greater thickness when applied to the skin.

[0040] When an internal crosslinking agent is used in crosslinking the crosslinked polymer that is the main component of the present crosslinked polymer particles, the timing of the internal crosslinking is not particularly limited, but it is preferable to carry out internal crosslinking by adding an internal crosslinking agent to the reaction system during polymerization of the monomer (composition) that is the raw material of the crosslinked polymer. In this case, the amount of the internal crosslinking agent used is suitably set within the range of preferably 0.0001% by mass to 10% by mass, more preferably 0.001% by mass to 1% by mass, and even more preferably 0.01% by mass to 1% by mass, based on the total amount of the monomer composition containing the internal crosslinking agent. By setting the amount of the internal crosslinking agent used within the above range, a crosslinked polymer having suitable thickening properties can be obtained, and an increase in water-soluble content due to a decrease in gel strength, an excessive decrease in thickening properties, and a decrease in handleability after absorption can be suppressed.

[0041] In addition, in the crosslinking of the crosslinked polymer, which is the main component of the crosslinked polymer particles, it is preferable to use a compound having two ethylenically unsaturated groups in one molecule as an internal crosslinking agent. On the other hand, from the viewpoint of good spreadability when applying a cosmetic containing the crosslinked polymer particles, it is preferable to use a compound having three or more ethylenically unsaturated groups in one molecule in a predetermined amount or less. Specifically, in the crosslinking of the crosslinked polymer, which is the main component of the crosslinked polymer particles, the amount of the compound having three or more ethylenically unsaturated groups in one molecule is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less, based on the total amount of the monomer composition including the internal crosslinking agent. In addition, the lower limit is not particularly limited, and may be 0% by mass.

[0042] In addition, when a compound having two ethylenically unsaturated groups in one molecule and a compound having three or more ethylenically unsaturated groups in one molecule are used as the internal crosslinking agent, the mass ratio of the compound having two ethylenically unsaturated groups in one molecule to the compound having three or more ethylenically unsaturated groups in one molecule in the internal crosslinking agent (mass of the compound having two ethylenically unsaturated groups in one molecule / mass of the compound having three or more ethylenically unsaturated groups in one molecule) is preferably 80 / 20 to 100 / 0, more preferably 90 / 10 to 100 / 0, and even more preferably 95 / 5 to 100 / 0.

[0043] In the crosslinking of the crosslinked polymer which is the main component of the present crosslinked polymer particle, the crosslinking agent usable as the surface crosslinking agent is not particularly limited, but an organic or inorganic surface crosslinking agent is preferably used. Among them, from the viewpoint of the physical properties of the obtained crosslinked polymer and the handling of the surface crosslinking agent, an organic surface crosslinking agent which reacts with a carboxyl group is preferred. Specific examples of the organic surface crosslinking agent that reacts with a carboxyl group include polyhydric alcohols such as ethylene glycol, propylene glycol, glycerin, pentaerythritol, sorbitol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, 1,3-butanediol, 1,4-butanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,4-pentanediol, 1,6-hexanediol, 2,5-hexanediol, and trimethylolpropane; polyhydric amine compounds such as diethanolamine, triethanolamine, ethylenediamine, diethylenetriamine, and triethylenetetramine; ethylene glycol diglycidyl ether; and polyethylene glycol diglycidyl ether. Examples of the polyhydric glycidyl compounds include polyglycidyl ethers, glycerol polyglycidyl ethers, diglycerol polyglycidyl ethers, polyglycerol polyglycidyl ethers, propylene glycol diglycidyl ethers, and polypropylene glycol diglycidyl ethers; and polyhydric aziridine compounds such as 2,4-tolylene diisocyanate, ethylene carbonate (1,3-dioxolan-2-one), propylene carbonate (4-methyl-1,3-dioxolan-2-one), 4,5-dimethyl-1,3-dioxolan-2-one, (poly, di, or mono) 2-oxazolidinone, epichlorohydrin, epibromohydrin, diglycol silicate, and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate], but are not limited to these compounds. These organic surface cross-linking agents reactive with a carboxyl group may be used alone or in combination of two or more kinds.

[0044] Among the organic surface crosslinking agents that react with carboxyl groups, from the viewpoint of the handling of the surface crosslinking agent and the absorption performance of the crosslinked polymer, an organic compound having two or more functional groups that react with carboxyl groups and that forms a covalent bond by reaction with the carboxyl group is preferably selected.Specific examples of such organic compounds include polyhydric alcohol compounds, epoxy compounds, polyamine compounds, condensates of polyamine compounds and haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, alkylene carbonate compounds, polyglycidyl compounds, oxetane compounds, vinyl ether compounds, and cyclic urea compounds.

[0045] When a surface crosslinking agent is used in the crosslinking of the crosslinked polymer, which is the main component of the crosslinked polymer particles, the timing of the surface crosslinking is not particularly limited, but it is preferable to carry out the feudal crosslinking by adding the surface crosslinking agent to the raw polymer of the crosslinked polymer (in the case of carrying out internal crosslinking, the polymer already crosslinked internally). In this case, the amount of the surface crosslinking agent used (the total amount when using multiple types) is appropriately set within the range of preferably 0.001 parts by mass to 10 parts by mass, more preferably 0.01 parts by mass to 5 parts by mass, relative to 100 parts by mass of the target polymer. By setting the amount of the surface crosslinking agent used within this range, an optimal crosslinked structure can be formed in the surface layer of the crosslinked polymer, and crosslinked polymer particles with good handling properties can be obtained.

[0046] The present crosslinked polymer particles may contain unpolymerized monomers (residual monomers) in addition to the crosslinked polymer obtained by polymerizing a monomer composition containing (meth)acrylic acid (salt) and any monomer other than (meth)acrylic acid (salt). In this specification, the amount of unpolymerized monomer components contained in the present crosslinked polymer particles is referred to as the amount of residual monomers. The residual monomers that can be contained in the present crosslinked polymer particles may include monomers derived from the above-mentioned monomer composition as well as monomers derived from other sources (e.g., crosslinking agents). In other words, the amount of residual monomers in the present crosslinked polymer particles refers to the total amount of the residual monomers derived from the monomer composition and the residual monomers derived from other sources.

[0047] In general, when polymerizing a monomer composition, it is difficult to achieve a polymerization conversion rate of 100% in the polymerization reaction. Therefore, the obtained crosslinked polymer or the crosslinked polymer particles containing the crosslinked polymer contain a certain amount of residual monomer, although it depends on the polymerization conditions (temperature, polymerization initiator, polymerization time, etc.).

[0048] The present inventors, in their intensive study of crosslinked polymer particles for cosmetics or quasi-drugs, have found that by controlling the amount of residual monomer in the crosslinked polymer particles to a predetermined amount (specifically, 1000 ppm) or less, a compound containing the crosslinked polymer particles (e.g., cosmetics, quasi-drugs, etc.) can be imparted with excellent thickness when applied to skin or hair. In the past, in crosslinked polymer particles for cosmetics or quasi-drugs, the amount of residual monomer in the crosslinked polymer particles has not been particularly noted. In this situation, the finding by the present inventors that "by controlling the amount of residual monomer to a predetermined amount or less, excellent thickness can be imparted when applied to skin or hair" can be said to be a surprising discovery that cannot be predicted from the prior art.

[0049] The amount of residual monomer in the present crosslinked polymer particles is 1000ppm or less, preferably 750ppm or less, more preferably 500ppm or less, and even more preferably 300ppm or less, from the viewpoint of providing excellent thickness when applied to skin or hair.The lower limit of the amount of residual monomer is not particularly limited, and may be, for example, 1ppm or more or 0ppm.The amount of residual monomer in the crosslinked polymer particles can be measured by the method described in the examples.

[0050] The method for controlling (reducing) the amount of residual monomer in the present crosslinked polymer particles to 1000 ppm or less is not particularly limited, but it is possible to reduce the amount of residual monomer in the present crosslinked polymer particles by, for example, increasing the polymerization temperature when polymerizing the monomer composition, reducing the amount of crosslinking agent when crosslinking the polymer, increasing the drying temperature in the drying step described below, or the like.

[0051] The crosslinked polymer particles may contain additives for various purposes. For example, in order to improve the handling of the powder and the feel when made into a gel, the crosslinked polymer particles may contain organic or inorganic water-insoluble fine particles, water-soluble polymers, surfactants, polyhydric alcohols, water-soluble polyvalent metal salts, etc. In addition, in order to prevent deterioration and coloring of the gel, the crosslinked polymer particles may contain chelating agents, reducing agents, antioxidants, hydroxycarboxylic acids (salts), etc. In addition, the crosslinked polymer particles may contain UV absorbers, dyes, pigments, fragrances, etc.

[0052] The content (addition amount) of the additive in the present crosslinked polymer particles is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, based on 100% by mass of the total amount of the crosslinked polymer including the additive. When a plurality of types of additives are used in combination, the content (addition amount) of the additive is the total content (addition amount) of each additive.

[0053] The present crosslinked polymer particles can improve the feeling of use as a cosmetic, so among additives, it is preferable to contain silicon dioxide.When the present crosslinked polymer particles contain silicon dioxide, the content of silicon dioxide relative to 100 parts by mass of the present crosslinked polymer particles is preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, and even more preferably 0.1 parts by mass or less, from the viewpoint of excellent feeling of use as a cosmetic.When the present crosslinked polymer particles contain silicon dioxide, the lower limit of the content of silicon dioxide relative to 100 parts by mass of the crosslinked polymer particles is not particularly limited, but can be, for example, 0.0001 parts by mass or more, 0.001 parts by mass or more, or 0.01 parts by mass or more.

[0054] The shape of the crosslinked polymer particles is not particularly limited, and may be irregularly pulverized, or spherical or nearly spherical (elliptical, rugby ball, sausage, etc.), but the irregularly pulverized shape is preferable because it improves the transparency of the swelling liquid. From the above viewpoint, the ratio of irregularly pulverized particles in the total amount of 100% by mass of the crosslinked polymer particles is preferably 90% by mass or more, preferably 95% by mass or more, more preferably 99% by mass or more, and particularly preferably 100% by mass. In other words, the ratio of particles of a shape other than the irregularly pulverized shape (spherical or nearly spherical) in the total amount of 100% by mass of the crosslinked polymer particles is preferably less than 10% by mass, more preferably less than 5% by mass, even more preferably less than 1% by mass, and may be 0% by mass.

[0055] In this specification, the shape of the crosslinked polymer particles can be evaluated by the aspect ratio. In this specification, the crosslinked polymer particles being spherical or nearly spherical means that the aspect ratio of the crosslinked polymer particles is 1.0 to 1.2, and the crosslinked polymer particles being irregularly pulverized means that the aspect ratio of the crosslinked polymer particles is greater than 1.2. Therefore, from the above viewpoint, the aspect ratio of the present crosslinked polymer particles is preferably greater than 1.2, and more preferably 1.3 or more. The aspect ratio of the crosslinked polymer particles can be measured by the method described in the Examples. When the present crosslinked polymer particles have an aspect ratio in the above range, the transparency of the blend can be expected to be improved.

[0056] The irregularly pulverized crosslinked polymer particles can be produced, for example, by carrying out a pulverization step (and a classification step) described below.

[0057] From the viewpoint of the feeling when the present crosslinked polymer particle blend is applied to the skin, the volume average particle diameter D10 of the present crosslinked polymer particles is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 6 μm or more, and is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. From the above viewpoint, the volume average particle diameter D10 of the present crosslinked polymer particles is preferably 1 μm to 20 μm, more preferably 3 μm to 15 μm, and even more preferably 6 μm to 10 μm.

[0058] From the viewpoint of the feeling when the present crosslinked polymer particle blend is applied to the skin, the volume average particle diameter D50 of the present crosslinked polymer particles is preferably 8 μm or more, more preferably 9 μm or more, even more preferably 10 μm or more, and preferably 20 μm or less, more preferably 18 μm or less, and even more preferably 15 μm or less. From the above viewpoint, the volume average particle diameter D50 of the present crosslinked polymer particles is preferably 8 μm to 20 μm, more preferably 9 μm to 18 μm, and even more preferably 10 μm to 15 μm.

[0059] From the viewpoint of the feeling of use when the present crosslinked polymer particle blend is applied to the skin, the volume average particle diameter D90 of the present crosslinked polymer particles is preferably 9 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 25 μm or less. From the above viewpoint, the volume average particle diameter D90 of the present crosslinked polymer particles is preferably 9 μm to 50 μm, more preferably 10 μm to 40 μm, and even more preferably 15 μm to 25 μm.

[0060] In this specification, the volume average particle diameter "D10" means a particle diameter at which the cumulative frequency of the volume average particle diameter is 10 volume%, the volume average particle diameter "D50" means a particle diameter at which the cumulative frequency of the volume average particle diameter is 50 volume%, and the volume average particle diameter "D90" means a particle diameter at which the cumulative frequency of the volume average particle diameter is 90 volume%.

[0061] The volume average particle size of the crosslinked polymer particles in this specification is a value measured using a known method, for example, a value measured by the following method: using a laser diffraction scattering type particle size distribution analyzer LA-950 manufactured by HORIBA, ethyl acetate is used as the circulating solvent during measurement, the refractive index of the dispersion is 1.59, and the refractive index of the dispersion medium is 1.371. The median diameter (μm) is calculated from the particle size distribution on a volume basis obtained by the measurement, and the volume average particle size is calculated.

[0062] From the viewpoint of the feel when the crosslinked polymer particle formulation is applied to the skin, the half width of the volume average particle diameter of the present crosslinked polymer particles is preferably 3 μm to 20 μm, more preferably 5 μm to 19 μm, even more preferably 7 μm to 18 μm, and particularly preferably 8 μm to 16 μm.

[0063] When the half width of the volume average particle diameter of the present crosslinked polymer is within the above range, a good feeling of use can be expected in terms of the slimy feeling when applied to the skin and the stickiness when dried.

[0064] The half-value width of the volume average particle diameter of the crosslinked polymer particles can be measured by a known method, and for example, the half-value width can be calculated based on a particle size distribution graph obtained by measuring the volume average particle diameter. Specifically, the half-value of the frequency is calculated from the maximum frequency value, and the volume average particle diameter at the half-value is calculated from the approximate curve equation between two points including the half-value, and the difference between the calculated volume average particle diameters at the two points is taken as the half-value width.

[0065] From the viewpoint of transparency of the crosslinked polymer particle blend, the turbidity of the crosslinked polymer particle is preferably 50% or less, more preferably 25% or less, and even more preferably 10% or less. The lower limit of the turbidity of the crosslinked polymer particle is not particularly limited, and may be, for example, 0.01% or more, 0.1% or more, or 1% or more, and is preferably 0%.

[0066] The turbidity of the crosslinked polymer particles of the present invention can be measured by a known method, for example, by the following method: The turbidity of the crosslinked polymer particles can be measured using a haze meter NDH7000 manufactured by Nippon Denshoku Co., Ltd. The measurement solution can be prepared by preparing a 1% by mass dispersion of the crosslinked polymer particles using a Three-One Motor manufactured by HEIDON Co., Ltd. at 600 rpm for 30 minutes and filling the dispersion in a quartz cell with an optical path length of 10 mm. The measurement temperature can be set to 25°C.

[0067] The present crosslinked polymer particles may be crosslinked polymer particles having water swelling properties. In this specification, the phrase "crosslinked polymer particles having water swelling properties" means that the crosslinked resin particles have water absorption properties and have a water absorption capacity of 80 (g / g) or more.

[0068] The water absorption capacity of the present crosslinked polymer particles is not particularly limited, but is preferably 80 (g / g) to 500 (g / g), more preferably 150 (g / g) to 450 (g / g), and even more preferably 200 (g / g) to 400 (g / g). When the deionized water absorption capacity of the crosslinked polymer particles is 80 (g / g) to 500 (g / g), it can absorb a sufficient amount of liquid to obtain a soft gel.

[0069] The water absorption ratio of the crosslinked polymer particles can be measured by the following method. First, 25°C purified water (100ml) is added to 0.2g of the crosslinked polymer particles, and the mixture is stirred at 500rpm using a propeller (four blades with a diameter of 7cm). After the mixture is stirred for 30 minutes, the dispersion containing the swollen (water-absorbed) crosslinked polymer particles is filtered under reduced pressure at 4.5kpa using a 0.22μm filter, and the weight of the resulting mixture is measured and used as the weight at the time of water absorption. After the measurement, the collected dispersion is dried by heating at 150°C for 60 minutes, and the weight of the remaining portion is measured and used as the dry weight. The water absorption ratio of the crosslinked polymer particles is calculated based on the following formula. Water absorption capacity of crosslinked polymer particles=[weight after absorption (g)−dry weight (g)] / dry weight (g).

[0070] The soluble content of the crosslinked polymer particles is not particularly limited, but the soluble content per 100% by mass of the crosslinked polymer particles is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. The upper limit of the soluble content is not particularly limited, but it is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. By making the soluble content 50% by mass or less, excessive stickiness is not generated. The soluble content of the crosslinked polymer particles being 15% by mass or more means that the crosslinked polymer particles contain 15% by mass or more of soluble polymer components (specifically, crosslinked polymers with low crosslinking degree and aqueous solution, non-crosslinked polymers, and monomer components, etc., which are separated by the soluble content measurement method described below). A cosmetic or quasi-drug containing crosslinked polymer particles containing a predetermined amount or more of such a soluble polymer component has the advantages of good spreadability when applied to the skin or hair, imparting a plump feeling to the skin, and also having excellent emulsion stability.

[0071] The soluble content of the crosslinked polymer particles in this specification is a value measured by the following method: (1) First, as a pretreatment for the measurement, the crosslinked polymer particles are dried at 80°C for 3 hours in a vacuum dryer with a pressure reduction of 5 kPa; (2) 500 g of 0.9 mass% NaCl aqueous solution and a stirrer (8 mmφ×30 mm without ring) are placed in a 500 mL beaker and adjusted to rotate at 600 rpm; (3) 2.0 g of the crosslinked polymer particles are placed in the beaker over 1 minute and stirred at 25°C for 3 hours; (4) After stirring, the stirred liquid is filtered using filter paper (ADVANTEC, No. 2). If the filtration takes a long time, it can be divided and filtered using multiple funnels. (5) 80 g of the obtained filtrate is weighed out into a 100 mL beaker that has been previously weighed at 140° C., and dried for 16 hours in a hot air dryer (PHH102, manufactured by Espec Corp.) at 140° C., and the mass Wa (g) of the filtrate solids is measured; (6) The above operations (2) to (5) are repeated in the same manner without using the crosslinked polymer particles, and the mass Wb (g) of the filtrate solids is measured; (7) The soluble content of the crosslinked polymer particles is calculated by the following formula: Soluble fraction of crosslinked polymer particles (% by mass)=[((Wa−Wb) / 80)×500 / 2]×100.

[0072] The viscosity of a compound obtained by mixing the present crosslinked polymer particles with purified water to give 1% by mass is preferably 5,000 mPa·s or more, more preferably 10,000 mPa·s or more, and even more preferably 20,000 mPa·s or more, from the viewpoint of thickening when used as a cosmetic or quasi-drug, and is preferably 50,000 mPa·s or less, more preferably 30,000 mPa·s or less, and even more preferably 25,000 mPa·s or less, from the viewpoint of usability. In addition, in order to achieve both suitable thickening and usability when used as a cosmetic or quasi-drug, the viscosity of a compound obtained by mixing the crosslinked polymer particles with purified water to give 1% by mass is preferably 5,000 mPa·s to 50,000 mPa·s, more preferably 10,000 mPa·s to 30,000 mPa·s, and even more preferably 20,000 mPa·s to 25,000 mPa·s.

[0073] The viscosity of the blend containing the crosslinked polymer particles of the present invention can be measured by a known method, for example, using a B-type viscometer TVB-10 manufactured by Toki Sangyo Co., Ltd. under conditions of a rotor TM4, a rotation speed of 6 rpm, a measurement time of 60 seconds, and a temperature of 25°C.

[0074] For highly viscous compounds that are difficult to measure under the above conditions, the rotation speed can be changed to 1.5 rpm for measurement.

[0075] <Method of Manufacturing Crosslinked Polymer Particles> Hereinafter, the present method for producing crosslinked polymer particles (hereinafter, sometimes referred to as "the present production method") will be described in detail with reference to an example, but the present method for producing crosslinked polymer particles is not limited thereto.

[0076] (i) Preparation of monomer aqueous solution The present production method preferably includes a step of preparing an aqueous monomer solution. The step of preparing an aqueous monomer solution is a step of preparing an aqueous solution of a monomer (hereinafter referred to as an "aqueous monomer solution") that is a raw material of the crosslinked polymer contained in the crosslinked polymer particles (constituting the crosslinked polymer). In addition to the monomer, an internal crosslinking agent and other substances described later may be added to the aqueous monomer solution as necessary.

[0077] For the sake of convenience, an aqueous monomer solution is described in this section, but a monomer slurry liquid can also be used as long as the water absorption properties, etc. of the crosslinked polymer particles obtained as the final product are not reduced.

[0078] (monomer) In the step of preparing the aqueous monomer solution, a monomer composition containing (meth)acrylic acid and / or a (meth)acrylic acid salt is used as a monomer component from the viewpoint of the physical properties and productivity of the resulting (crosslinked) polymer. Specific aspects of the monomer composition containing (meth)acrylic acid and / or a (meth)acrylic acid salt used in the step of preparing the aqueous monomer solution are as described above. That is, the aqueous monomer solution may contain, in addition to (meth)acrylic acid (salt), a monomer other than (meth)acrylic acid (salt), an internal crosslinking agent, an additive, and the like. Specific aspects of these components are also as described above.

[0079] (Other substances added to the aqueous monomer solution) From the viewpoint of improving the physical properties of the resulting crosslinked polymer particles, the present production method preferably adds the following substances at one or more of the following points: when preparing the monomer aqueous solution, during the polymerization process, and after the polymerization process. Examples of the substances include, but are not limited to, hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salt), and crosslinked polyacrylic acid (salt), as well as foaming agents such as carbonates, azo compounds, and bubbles, surfactants, and chain transfer agents. These substances may be added alone or in combination of two or more.

[0080] The amount of other substances added when preparing the aqueous monomer solution is appropriately set within the range of preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (the lower limit is 0% by mass) based on the total amount of the monomers (including monomers other than (meth)acrylic acid (salt)).

[0081] In addition, when a water-soluble resin or a crosslinked polymer is used as the other substance, a graft polymer or a crosslinked polymer composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained, and these polymers and crosslinked polymer compositions are also included in the category of the crosslinked polymer according to one embodiment of the present invention.

[0082] (monomer component concentration) The concentration of the monomer component in the aqueous monomer solution prepared in the step of preparing the aqueous monomer solution is not particularly limited, but is appropriately set within the range of preferably 10% by mass to 80% by mass, more preferably 20% by mass to 75% by mass, and even more preferably 30% by mass to 70% by mass, from the viewpoint of the physical properties of the resulting crosslinked polymer.

[0083] In this specification, the "concentration of the monomer component" is a value calculated from the following formula 1, in which the mass of the aqueous monomer solution does not include the mass of the graft component, the crosslinked polymer, or the hydrophobic organic solvent in the reversed-phase suspension polymerization: Monomer component concentration (mass%) = (mass of monomer component) / (mass of monomer aqueous solution) × 100 (Equation 1) (ii) Polymerization process The present production method preferably includes a polymerization step in which the monomer components in the aqueous monomer solution obtained in the aqueous monomer solution preparation step are polymerized to obtain an aqueous gel-like polymer (when the aqueous monomer solution contains an internal crosslinking agent, an aqueous gel-like crosslinked polymer, hereinafter sometimes collectively referred to as "aqueous gel").

[0084] (Polymerization initiator) In the polymerization step, it is preferable to carry out polymerization of the above-mentioned monomer components using a polymerization initiator. Examples of polymerization initiators that can be used in the polymerization step include thermal decomposition type polymerization initiators, photodecomposition type polymerization initiators, and redox-based polymerization initiators that are used in combination with a reducing agent that promotes the decomposition of these polymerization initiators. For example, polymerization initiators described in U.S. Pat. No. 7,265,190 and the like are applied. From these, one or more polymerization initiators are selected in consideration of the polymerization form and the like. More specifically, as the polymerization initiator, preferably a peroxide or an azo compound, more preferably a peroxide, and even more preferably a persulfate are suitably selected from the viewpoint of the handling of the polymerization initiator and the physical properties of the crosslinked polymer. The amount of the polymerization initiator used in the polymerization step is appropriately set within a range of preferably 0.001 to 1 part by mass, more preferably 0.001 to 0.5 parts by mass, based on 100 parts by mass of the total monomer (including other monomers). When a reducing agent is used in combination, the amount of the reducing agent used is appropriately set within a range of preferably 0.0001 to 0.02 parts by mass, based on 100 parts by mass of the total monomer (including other monomers). By setting the amounts of the polymerization initiator and reducing agent used within the ranges, a crosslinked polymer having the desired performance can be produced.

[0085] In the polymerization step, the polymerization reaction of the monomer components may be initiated by irradiation with active energy rays such as radiation, electron beams, ultraviolet rays, etc. Alternatively, polymerization may be carried out by using both active energy ray irradiation and a polymerization initiator.

[0086] (polymerization form) The polymerization form of the monomer aqueous solution applied in the polymerization step is not particularly limited, but examples thereof include aqueous solution polymerization, reversed-phase suspension polymerization, spray polymerization, droplet polymerization, bulk polymerization, and precipitation polymerization. Among these, taking into consideration the controllability of polymerization and the water absorption performance of the crosslinked polymer, preferably aqueous solution polymerization or reversed-phase suspension polymerization, more preferably aqueous solution polymerization, and even more preferably continuous aqueous solution polymerization is selected. Specific examples of continuous aqueous solution polymerization include continuous belt polymerization described in U.S. Pat. No. 4,893,999 and continuous kneader polymerization described in U.S. Pat. No. 6,987,151. Crosslinked polymers can be produced with high productivity by these continuous aqueous solution polymerizations.

[0087] Although each of the above polymerization modes can be carried out in an air atmosphere, from the viewpoint of preventing coloration of the resulting crosslinked polymer, it is preferably carried out in an inert gas atmosphere such as nitrogen or argon (for example, oxygen concentration is 1% by volume or less). Dissolved oxygen in the aqueous monomer solution is also preferably sufficiently replaced with an inert gas (for example, the amount of dissolved oxygen is less than 1 mg / l).

[0088] The polymerization step in the present production method may be in the form of alkaline polymerization in which a monomer composition containing acrylic acid (salt) having a desired neutralization rate (pre-neutralized) is polymerized, or in the form of acid polymerization in which a monomer composition containing acrylic acid (salt) having a neutralization rate lower than the desired neutralization rate or unneutralized acrylic acid is polymerized. However, the alkaline polymerization is preferred because it can improve the uniformity of the crosslinking degree in the crosslinked polymer, and as a result, it can improve the smoothness of the compound containing the obtained crosslinked polymer particles.

[0089] In the polymerization step, in addition to the polymerization reaction, the (internal) crosslinking reaction of the crosslinked polymer may be allowed to proceed. That is, in the polymerization step, an internal crosslinking agent may be added in advance when preparing the monomer aqueous solution, and a crosslinking reaction (crosslinking polymerization) may be allowed to proceed simultaneously with the polymerization reaction, or polymerization may be performed without adding an internal crosslinking agent, and an internal crosslinking agent may be added during or after the polymerization to allow the crosslinking reaction to proceed. These methods may also be used in combination.

[0090] In the polymerization step, the temperature at which the polymerization reaction is carried out (polymerization temperature (i.e., the temperature of the reaction liquid in the reaction apparatus)) is not particularly limited, but is preferably 50° C. or higher, more preferably 60° C. or higher, and even more preferably 70° C. or higher. When a crosslinking reaction is carried out simultaneously with the polymerization reaction, the polymerization temperature is set to 80° C. or higher, whereby the crosslinking polymerization can be carried out more efficiently, and as a result, crosslinked polymer particles having a lower amount of residual monomer can be provided.

[0091] (iii) Gel crushing process The present production method preferably includes a gel crushing step in which the hydrogel obtained in the polymerization step is crushed to obtain a particulate hydrogel (hereinafter referred to as "particulate hydrogel"). The "gel crushing" refers to converting the hydrogel into particles using a gel crusher such as a kneader, meat chopper, or cutter mill. Regarding the embodiment and conditions of the gel crushing, for example, the contents described in International Publication No. 2011 / 126079 and the like are applied to one embodiment of the present invention.

[0092] In addition, when kneader polymerization is selected as the polymerization form, the polymerization step and the gel crushing step are carried out simultaneously. In addition, when a particulate hydrogel is obtained in the polymerization process, such as in reversed-phase suspension polymerization or droplet polymerization, the gel crushing step may not be carried out.

[0093] Therefore, the hydrogel obtained in the polymerization step is subjected to the next step, the drying step, either in the form of particles as it is or in the form of particles obtained by gel pulverization. The mass average particle diameter (D50) of the particulate hydrogel (measured in accordance with paragraph

[0255] (d) of WO 2011 / 126079, "Weight average particle diameter (D50) and logarithmic standard deviation (σζ) of particle size distribution") is appropriately set within a range of preferably 0.1 mm to 50 mm, more preferably 0.1 mm to 10 mm, and even more preferably 0.2 mm to 5 mm, from the viewpoint of drying efficiency.

[0094] (iv) Drying process The present production method preferably includes a drying step in which the particulate hydrogel obtained in the polymerization step or the particulate hydrogel obtained in the gel crushing step is dried to a solid content in a desired range to obtain a dried polymer. The desired solid content in the drying step is not particularly limited, but is appropriately set within a range of preferably 80% by mass or more, more preferably 85% to 99% by mass, even more preferably 90% to 98% by mass, and particularly preferably 92% to 97% by mass. Here, the "solid content" is a value calculated from the drying loss of the particulate hydrogel (the change in mass when 1 g of the sample is dried at 180°C for 3 hours), and is calculated from the following (Equation 2). Solid content (mass%) = (sample mass (1 g) - loss on drying) / (sample mass (1 g)) × 100 (Equation 2) In the drying step, the method for drying the particulate hydrogel is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferably selected, and more preferably band drying in which hot air drying is performed on a ventilation belt is selected.

[0095] The drying conditions in the drying step are not particularly limited, but from the viewpoint of drying efficiency and color tone of the crosslinked polymer, as well as from the viewpoint of obtaining crosslinked polymer particles with a smaller amount of residual monomer, the drying temperature is preferably set appropriately within the range of 120°C to 250°C, more preferably 150°C to 200°C, and the drying time is preferably set appropriately within the range of 10 minutes to 120 minutes, more preferably 20 minutes to 90 minutes, and even more preferably 30 minutes to 60 minutes. The drying temperature is usually determined by the temperature of the heat medium (for example, in the case of hot air drying, it is determined by the temperature of the hot air), but in the case of drying that cannot be determined by the temperature of the heat medium, such as microwave drying, it is determined by the temperature of the particulate hydrogel. The drying temperature may be a constant temperature or may be changed appropriately during drying.

[0096] Drying conditions other than the drying temperature and drying time in the drying step may be appropriately set depending on the moisture content of the particulate hydrogel, the amount of the particulate hydrogel to be supplied to the drying step, the target solid content, etc. When band drying is selected, for example, the conditions described in International Publication No. 2006 / 100300 and the like are suitably applied to one embodiment of the present invention.

[0097] (v) Grinding process, classification process The present production method preferably includes a pulverization step and a classification step in which the dried polymer obtained in the drying step is pulverized (pulverization step) and adjusted to a particle size in a desired range (classification step) to obtain crosslinked polymer particles having a desired particle size. The pulverization step differs from the gel pulverization step (iii) in that the dried polymer to be pulverized has been subjected to a drying step.

[0098] In the pulverization step, the method of pulverizing the dried polymer is not particularly limited, but it is preferable to pulverize the dried polymer using a pulverizer. The pulverizer that can be used in the pulverization step may be either a continuous type or a batch type, and specifically includes a roll mill, a vibration mill, a ball mill, a hammer mill, a pin mill, a flash mill, a jet mill, etc. In addition, the ball mill is not limited to a type that uses only spherical balls, and is a broad concept including a rod mill and a compound mill. Preferred pulverizers are pulverizers in which the material to be pulverized in the air or in a dropped state breaks due to impact and the parts of the pulverizer do not come into contact with each other, and specifically include a pin mill, a flash mill, and a jet mill. These three preferred types of pulverizers have the advantage that the temperature rise of the material to be pulverized during pulverization is small, so that the deterioration of the crosslinked polymer particles is suppressed, and the pulverizer itself is hardly worn or damaged, so that the product after pulverization is less likely to be mixed with foreign matter. Jet mills include a fluidized bed jet mill, a collision plate jet mill, a rotary mechanical mill, etc., and preferably a fluidized bed jet mill, especially an airflow jet mill. When an airflow jet mill is used, the grinding pressure is, for example, 0.01 MPa or more, preferably 0.05 MPa or more, and more preferably 0.1 MPa or more. The upper limit of the grinding pressure is, for example, 3 MPa or less, preferably 1 MPa or less, and more preferably 0.7 MPa or less.

[0099] When the particle size of the crosslinked polymer particles is controlled finely (specifically, so that the volume average particle size is about 8 μm to 20 μm), it is preferable to carry out multi-stage pulverization in the pulverization step. More specifically, it is preferable to carry out a first pulverization step in which the dried polymer is coarsely pulverized, and then a second or subsequent pulverization step (which may be carried out once or twice or more) in which the coarsely pulverized dried polymer is further pulverized finely. When carrying out multi-stage pulverization, it is preferable to pulverize the dried polymer using a combination of multiple types of pulverizers. The combination of pulverizers in multi-stage pulverization varies depending on the particle size before pulverization and the target particle size, but the pulverizer used in the first pulverization step is preferably a roll mill, a vibration mill, a hammer mill, or a pin mill. In addition, in order to obtain a crosslinked polymer with a fine average particle size, it is preferable to carry out the final pulverization step using a jet mill or a ball mill, more preferably a jet mill. In this specification, the final pulverization step may be referred to as fine pulverization. It is also preferable to carry out a pulverization step using a flash mill between the first pulverization step and the final pulverization step.

[0100] From the viewpoint of pulverization efficiency, it is preferable to adjust the inner wall temperature of the pulverization chamber in each pulverization step. The inner wall temperature of the pulverization chamber is preferably 30 to 150° C., more preferably 35 to 120° C., and particularly preferably 40 to 100° C. By adjusting the inner wall temperature of the pulverization chamber to the above temperature, the crosslinked polymer particles are less likely to adhere to each other, and are easily discharged from the pulverizer.

[0101] The relative humidity in the grinding chamber is preferably 70% RH or less, more preferably 50% RH or less, and even more preferably 30% RH or less. When using a grinding machine that supplies gas to the grinding chamber, such as a jet mill, the dew point of the gas is preferably 0° C. or less, more preferably −5 to −80° C., and particularly preferably −10 to −50° C. Other operating conditions may be appropriately set in consideration of the particle size and processing amount of the material to be ground, the size of the grinding machine, and the like.

[0102] In the present production method, it is preferable to remove coarse crosslinked polymer particles that do not have the desired particle size by introducing a classification step. The classification method of the crosslinked polymer particles in the classification step is not particularly limited, but for example, a method using a classifier can be mentioned. The equipment (classifier) ​​that can be used in the classification step is not particularly limited, but for example, a sieve classifier and an air flow classifier can be mentioned. Furthermore, a machine having a pulverizing function, for example, a turbo screener (manufactured by Matsubo Co., Ltd.), can also be used, in which case the pulverizing step and the classification step can be carried out simultaneously. The classification step can be carried out simultaneously with the pulverizing step, before the pulverizing step for the purpose of removing coarse particles that are difficult to pulverize, and / or after the pulverizing step for the purpose of removing particles larger than the particle size desired for the present crosslinked polymer particles. Furthermore, when the pulverization is performed in multiple stages, it can also be carried out between each pulverizing step. The crosslinked polymer particles that do not have the desired particle size removed in the classification step are preferably subjected to the pulverizing step again in order to reduce loss.

[0103] The particle size of the crosslinked polymer particles can be appropriately adjusted not only in the pulverization step and the classification step but also in the polymerization step (particularly in the case of reversed-phase suspension polymerization or droplet polymerization).

[0104] (vi) Surface crosslinking process The present production method preferably includes a surface cross-linking step in which the cross-linked polymer particles after drying and pulverization (and classification) are surface cross-linked for the purpose of improving the water absorption rate and liquid dispersibility. The surface cross-linking step can be said to be a step of further providing a portion with high cross-link density on the surface layer of the cross-linked polymer particles after drying, and is composed of, for example, a mixing step and a heat treatment step. In the surface cross-linking step, radical cross-linking and / or monomer polymerization in the surface layer of the cross-linked polymer particles, a cross-linking reaction between the surface layer of the cross-linked polymer particles and a surface cross-linking agent, etc. are performed to obtain surface-cross-linked cross-linked polymer particles. In addition, the surface cross-linking step is also a step performed for the purpose of improving the handleability of the cross-linked polymer particles after drying during pulverization, and may be performed on the cross-linked polymer particles before pulverization to the particle size of the final product, for example, on the pulverized intermediate. In this case, the surface cross-linked layer does not necessarily have to remain on the surface of the cross-linked polymer particles of the final product.

[0105] (vi-1) Mixing process The surface cross-linking step preferably includes a mixing step in which a surface cross-linking agent is mixed with the dried and pulverized cross-linked polymer particles to obtain a moist mixture.

[0106] (Surface cross-linking agent) The compounds that can be used as the surface crosslinking agent in the mixing step and their compositions are as described above.

[0107] In the mixing step, it is preferable to add the surface crosslinking agent to the crosslinked polymer particles in the form of an aqueous solution (surface crosslinking agent solution). In this case, the amount of the surface crosslinking agent solution used is appropriately set within a range of preferably 0.1 to 20 parts by mass, more preferably 0.3 to 15 parts by mass, and even more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the crosslinked polymer particles. By setting the amount of the surface crosslinking agent solution used within this range, the handleability of the surface crosslinking agent solution is improved, and the surface crosslinking agent can be evenly mixed with the crosslinked polymer particles.

[0108] (vi-2) Heat treatment process The surface cross-linking step preferably includes a heat treatment step in which the humidified mixture obtained in the mixing step is heat-treated to obtain surface-cross-linked cross-linked polymer particles.

[0109] (Heat treatment method) In the heat treatment step, the method of heating the humidified mixture is not particularly limited, and for example, the humidified mixture may be heated in a stationary state, or may be heated under stirring and mixing using a mixing means such as stirring. From the viewpoint of being able to heat the entire humidified mixture evenly, it is preferable to heat under stirring and mixing. In addition, preferred examples of the apparatus used in the heat treatment step include a mortar mixer, a paddle dryer, a multi-fin processor, and a tower dryer.

[0110] The heating temperature in the heat treatment step may be set according to the type and amount of the surface cross-linking agent used, the absorption performance of the intended cross-linked polymer particles, etc., and is not particularly limited, but may be appropriately set within a range of preferably 70° C. to 250° C., more preferably 90° C. to 210° C. as the heat medium temperature. In addition, the heating time is also not particularly limited, but may be appropriately set within a range of preferably 1 minute to 2 hours.

[0111] (viii) Addition of other additives The present production method may include a step of adding other additives other than the additives described above in order to impart various functions to the crosslinked polymer particles. Specific examples of other additives include polyvalent metal salt compounds, α-hydroxycarboxylic acid compounds, surfactants, compounds having phosphorus atoms, oxidizing agents, organic reducing agents, water-insoluble inorganic fine particles, organic powders such as metal soaps, pulp and thermoplastic fibers, deodorants, antibacterial agents, bactericidal components, fragrances, foaming agents, pigments, dyes, plasticizers, adhesives, fertilizers, salts, cationic polymers, hydrophilic polymers such as polyethylene glycol and polyethyleneimine, hydrophobic molecules such as paraffin, thermoplastic resins such as polyethylene and polypropylene, and thermosetting resins such as polyester resins and urea resins. As the surfactants, the compounds disclosed in International Publication No. 2005 / 075070 are preferably used.

[0112] The amount of additive used (addition amount) in the other additive addition process is appropriately determined depending on the application, so is not particularly limited, but is preferably 3 parts by mass or less, more preferably 1 part by mass or less, per 100 parts by mass of the crosslinked polymer particles.

[0113] (ix) Other processes In addition to the above-mentioned steps, the present manufacturing method may include a humidification step, a granulation step, a sizing step, a fine powder removal step, a fine powder reuse step, etc. as necessary. In addition, the present manufacturing method may further include one or more steps such as a transport step, a storage step, a packaging step, and a storage step. The "sizing step" includes a fine powder removal step after the surface crosslinking step, and a step of classifying and pulverizing when the crosslinked polymer aggregates and exceeds a desired size. In addition, the humidification step is a step of adding water to the crosslinked polymer particles to increase the water content, and the handling of the crosslinked polymer particles may be improved by carrying out the humidification step. The water added in the humidification step may be liquid water or water vapor, or may be an aqueous solution or a fine particle dispersion.

[0114] <Application> The present invention can impart excellent thickness when applied to skin or hair, and a cosmetic or quasi-drug containing the present crosslinked polymer particles can also be expected to have the effect of imparting excellent thickness when applied to skin or hair. That is, in one embodiment of the present invention, a cosmetic or quasi-drug containing the present crosslinked polymer particles (hereinafter, sometimes referred to as "the present cosmetic or quasi-drug") is provided. The present cosmetic or quasi-drug can impart excellent thickness when applied to skin or hair. Therefore, it is preferable to use the present crosslinked polymer particles as a cosmetic or quasi-drug for skin, or as a cosmetic or quasi-drug for hair.

[0115] The skin cosmetics and quasi-drugs may be in any form, such as liquid, gel, cream, semi-solid, solid, stick, or powder, and may be skin cosmetics and quasi-drugs such as milk lotions, creams, lotions, beauty essences, packs, facial cleansers, and makeup cosmetics.

[0116] Examples of the cosmetic preparation according to one embodiment of the present invention include skin cosmetic preparations, external skin preparations, hair cosmetic preparations, and external hair preparations.

[0117] The content of the present crosslinked polymer particles in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 2.0 parts by mass or more, from the viewpoint of imparting excellent thickness. The upper limit of the content of the present crosslinked polymer particles in 100 parts by mass of the present cosmetic or quasi-drug is not particularly limited, but may be, for example, 20.0 parts by mass or less, 10.0 parts by mass or less, or 5.0 parts by mass or less.

[0118] The present cosmetic or quasi-drug may contain compounds other than the present crosslinked polymer particles, such as thickeners, powder components, pH adjusters, nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, oils, moisturizers, water-soluble polymers, antioxidants, UV absorbers, chelating agents, preservatives, antibacterial agents, colorants, and fragrances.

[0119] Examples of thickeners that may be contained in the present cosmetic or quasi-drug include dextrin, sodium pectinate, sodium alginate, PVM (methyl vinyl ether), locust bean gum, tamarind gum, dialkyldimethylammonium cellulose sulfate, aluminum magnesium silicate, bentonite, hectorite, AlMg silicate (beegum), laponite, and anhydrous silicic acid.

[0120] The content of the thickener contained in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.001 parts by mass or more, more preferably 0.005 parts by mass or more, even more preferably 0.05 parts by mass or more, preferably 3 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.5 parts by mass or less. The content of the thickener contained in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.001 to 3 parts by mass, more preferably 0.005 to 1 part by mass, and even more preferably 0.05 to 0.5 parts by mass.

[0121] Examples of powder components that may be contained in the present cosmetic or quasi-drug include inorganic powders (e.g., talc, kaolin, mica, sericite, muscovite, phlogopite, synthetic mica, red mica, biotite, vermiculite, magnesium carbonate, calcium carbonate, aluminum silicate, barium silicate, calcium silicate, magnesium silicate, strontium silicate, metal tungstate, magnesium, silica, zeolite, barium sulfate, calcined calcium sulfate (calcined gypsum), calcium phosphate, fluorapatite, hydroxyapatite, ceramic powder, metal stone, etc.) Soap (e.g., zinc myristate, calcium palmitate, aluminum stearate), boron nitride, etc.); organic powders (e.g., polyamide resin powder (nylon powder), polyethylene powder, polymethyl methacrylate powder, polystyrene powder, styrene and acrylic acid copolymer resin powder, benzoguanamine resin powder, polytetrafluoroethylene powder, cellulose powder, etc.); inorganic white pigments (e.g., titanium dioxide, zinc oxide, etc.); inorganic red pigments (e.g., iron oxide (red oxide), iron titanate, etc.); inorganic brown pigments (e.g., gamma-iron oxide, etc.); inorganic yellow pigments (e.g., yellow iron oxide, yellow ochre, etc.; inorganic black pigments (e.g., black iron oxide, low-order titanium oxide, etc.); inorganic purple pigments (e.g., mango violet, cobalt violet, etc.); inorganic green pigments (e.g., chromium oxide, chromium hydroxide, cobalt titanate, etc.); inorganic blue pigments (e.g., ultramarine, Prussian blue, etc.); pearl pigments (e.g., titanium oxide coated mica, titanium oxide coated bismuth oxychloride, titanium oxide coated talc, colored titanium oxide coated mica, bismuth oxychloride, fish scale foil, etc.); metal powder pigments (e.g., aluminum powder, copper powder, etc.) organic pigments such as zirconium, barium or aluminum lakes (e.g. organic pigments such as Red 201, Red 202, Red 204, Red 205, Red 220, Red 226, Red 228, Red 405, Orange 203, Orange 204, Yellow 205, Yellow 401, and Blue 404, Red 3, Red 104, Red 106, Red 227, Red 230, Red 401, Red 505, Orange 205, Yellow 4, Yellow 5, Yellow 202, Yellow 203, Green 3, and Blue 1, etc.); natural pigments (e.g. chlorophyll, beta-carotene, etc.);etc.;

[0122] Examples of pH adjusters that may be contained in the present cosmetic or quasi-drug include mixtures of hydroxycarboxylic acids and their alkali metal salts, such as lactic acid-sodium lactate and citric acid-sodium citrate; mixtures of dicarboxylic acids and their alkali metal salts, such as succinic acid-sodium succinate; alkali metal hydroxides, such as sodium hydroxide and potassium hydroxide, ammonia (which may be aqueous ammonia), citric acid, tartaric acid, lactic acid, phosphoric acid, neutral amino acids (e.g., threonine, cysteine, etc.), sodium acyl sarcosine (sodium lauroyl sarcosine), acyl glutamate, sodium acyl-β-alanine, glutathione, pyrrolidone carboxylic acid, and the like.

[0123] The content of the pH adjuster contained in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.001 parts by mass or more, more preferably 0.005 parts by mass or more, even more preferably 0.01 parts by mass or more, and preferably 3 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.5 parts by mass or less. The content of the pH adjuster contained in 100 parts by mass of the cosmetic or quasi-drug according to one embodiment of the present invention is preferably 0.001 to 3 parts by mass, more preferably 0.005 to 1 part by mass, and even more preferably 0.01 to 0.5 parts by mass.

[0124] The present cosmetic or quasi-drug preferably contains an inorganic white pigment, since this makes it possible to provide a preparation (particularly a suncare preparation) that is highly stable and has an excellent feel when used.

[0125] The mass ratio of the present crosslinked polymer particles to the inorganic white pigment in the present cosmetic or quasi-drug (mass of the present crosslinked polymer particles / mass of the inorganic white pigment) may be 1 / 3 to 1 / 30, 1 / 5 to 1 / 20, or 1 / 8 to 1 / 15. Here, the mass of the present crosslinked polymer particles means the mass of the present crosslinked polymer particles after drying. Specifically, the present crosslinked polymer particles after drying can be obtained by drying the present crosslinked polymer particles in a hot air dryer at a temperature of 150°C to 200°C for a certain period of time (for example, about 30 minutes to 90 minutes).

[0126] Examples of nonionic surfactants that may be contained in the present cosmetic or quasi-drug include POE sorbitan fatty acid esters (e.g., POE sorbitan monooleate, POE sorbitan monostearate, POE sorbitan monooleate, POE sorbitan tetraoleate, etc.); POE sorbit fatty acid esters (e.g., POE sorbitan monolaurate, POE sorbitan monooleate, POE sorbitan pentaoleate, POE sorbitan monostearate, etc.); POE glycerin fatty acid esters (e.g., POE glycerin monostearate, POE sorbitan tetraoleate, etc.); POE monooleates such as POE stearate, POE glycerin monoisostearate, and POE glycerin triisostearate; POE fatty acid esters (e.g., POE distearate, POE monodioleate, POE monostearate (e.g., PEG-20 stearate), ethylene glycol distearate, etc.); POE alkyl ethers (e.g., POE lauryl ether, POE oleyl ether, POE stearyl ether, POE-behenyl ether, POE-2-octyldodecyl ether, POE cholestanol ether, etc. etc.); Pluronic (registered trademark) mold agent etc.; POE·POP alkyl ethers (e.g., POE·POP cetyl ether, POE·POP-2-decyltetradecyl ether, POE·POP monobutyl ether, POE·POP hydrogenated lanolin, POE·POP glycerin ether etc.); tetraPOE·tetraPOP ethylenediamine condensates (e.g., Tetronic etc.); POE castor oil, POE hydrogenated castor oil, or derivatives thereof (e.g., POE castor oil, POE hydrogenated castor oil, POE hydrogenated castor oil monoisostearate, POE hydrogenated castor oil, etc.); hydrogenated castor oil triisostearate, POE hydrogenated castor oil monopyroglutamic acid monoisostearate diester, POE hydrogenated castor oil maleic acid, etc.); POE beeswax or POE lanolin derivatives (e.g., POE sorbitol beeswax, etc.); alkanolamides (e.g., coconut oil fatty acid diethanolamide, lauric acid monoethanolamide, fatty acid isopropanolamide, etc.); POE propylene glycol fatty acid esters; POE alkylamines; POE fatty acid amides; sucrose fatty acid esters; alkylethoxydimethylamine oxides;trioleyl phosphate, sorbitan fatty acid esters (e.g., sorbitan monooleate, sorbitan monoisostearate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan sesquioleate, sorbitan trioleate, diglycerol sorbitan penta-2-ethylhexyl acid, diglycerol sorbitan tetra-2-ethylhexyl acid, etc.); glycerin fatty acids (e.g., glycerin monocottonseed oil fatty acid, glycerin monoerucate, glycerin sesquioleate, glycerin monostearate, α,α'-oleic acid pyroglutamic acid glycerin, glycerin monostearate malic acid, polyglyceryl monoisostearate, polyglyceryl diisostearate, etc.); propylene glycol fatty acid esters (e.g., propylene glycol monostearate, etc.); hydrogenated castor oil derivatives; glycerin alkyl ethers, etc. The above "POE" represents a polyethylene glycol residue (when two hydroxyl groups are bonded, it becomes a polyoxyethylene unit. When one hydroxyl group is bonded, it becomes a polyoxyethylene unit having a hydroxyl group at the end), and the above "POP" represents a polypropylene glycol residue (when two hydroxyl groups are bonded, it becomes a polyoxypropylene unit. When one hydroxyl group is bonded, it becomes a polyoxypropylene unit having a hydroxyl group at the end). POE·POP means POE or POP. ;

[0127] Examples of anionic surfactants that may be contained in the present cosmetic or quasi-drug include fatty acid soaps (e.g., sodium laurate, sodium palmitate, etc.); higher alkyl sulfates (e.g., sodium lauryl sulfate, potassium lauryl sulfate, etc.); alkyl ether sulfates (e.g., POE triethanolamine lauryl sulfate, sodium POE lauryl sulfate, etc.); N-acylsarcosinates (e.g., sodium lauroyl sarcosinate, etc.); higher fatty acid amide sulfonates (e.g., sodium N-myristoyl-N-methyl taurine, sodium coconut oil fatty acid methyl tauride, sodium lauryl methyl tauride, etc.); phosphates (sodium POE oleyl ether phosphate, sodium POE stearyl ether phosphate, etc.); sulfosuccinates (e.g., sodium di-2-ethylhexyl sulfosuccinate, sodium monolauroyl monoethanolamide polyoxyethylene sulfosuccinate, sodium lauryl polypropylene glycolate, sodium lauryl methyl tauride, sodium lauryl methyl tauride, etc.). sodium aryl sulfosuccinate, etc.); alkylbenzene sulfonates (e.g., sodium linear dodecylbenzene sulfonate, triethanolamine linear dodecylbenzene sulfonate, linear dodecylbenzene sulfonic acid, etc.); higher fatty acid ester sulfate salts (e.g., sodium hydrogenated coconut oil fatty acid glycerin sulfate, etc.); N-acyl glutamates (e.g., monosodium N-lauroyl glutamate, disodium N-stearoyl glutamate, monosodium N-myristoyl-L-glutamate, etc.); sulfated oils (e.g., turmeric oil, etc.); POE alkyl ether carboxylic acids; POE alkyl allyl ether carboxylates; α-olefin sulfonates; higher fatty acid ester sulfonates; secondary alcohol sulfate salts; higher fatty acid alkylolamide sulfate salts; sodium lauroyl monoethanolamide succinate; ditriethanolamine N-palmitoyl aspartate; sodium caseinate; and the like.

[0128] Examples of cationic surfactants that may be contained in the present cosmetic or quasi-drug include alkyltrimethylammonium salts (e.g., stearyltrimethylammonium chloride, lauryltrimethylammonium chloride, etc.); alkylpyridinium salts (e.g., cetylpyridinium chloride, etc.); distearyldimethylammonium chloride dialkyldimethylammonium salts; poly(N,N'-dimethyl-3,5-methylenepiperidinium chloride); alkyl quaternary ammonium salts; alkyldimethylbenzylammonium salts; alkylisoquinolinium salts; dialkylmorphonium salts; POE alkylamines; alkylamine salts; polyamine fatty acid derivatives; amyl alcohol fatty acid derivatives; benzalkonium chloride; benzethonium chloride; and the like.

[0129] Examples of amphoteric surfactants that may be contained in the present cosmetic or quasi-drug include imidazoline-based amphoteric surfactants (e.g., 2-undecyl-N,N,N-(hydroxyethylcarboxymethyl)-2-imidazoline sodium, 2-cocoyl-2-imidazolinium hydroxide-1-carboxyethyloxy disodium salt, etc.); betaine-based surfactants (e.g., 2-heptadecyl-N-carboxymethyl-N-hydroxyethylimidazolinium betaine, lauryl dimethylaminoacetic acid betaine, alkyl betaine, amido betaine, sulfobetaine, etc.); and the like.

[0130] The content of the surfactant contained in 100 parts by mass of the present cosmetic or quasi-drug (when multiple types of surfactants are contained, the total amount of them) is preferably 0.0001 parts by mass or more, more preferably 0.0005 parts by mass or more, even more preferably 0.001 parts by mass or more, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 1 part by mass or less. The content of the surfactant contained in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.0001 parts by mass to 3 parts by mass, more preferably 0.0005 parts by mass to 1 part by mass, and even more preferably 0.001 parts by mass to 0.5 parts by mass.

[0131] The oils that may be contained in the present cosmetic or quasi-drug are not particularly limited, but examples thereof include fatty acids, oils and fats, ester oils, silicone oils, and hydrocarbon oils. These components may be used alone or in appropriate combinations of two or more types.

[0132] Examples of fatty acids that may be contained in the present cosmetic or quasi-drug include lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, behenic acid, undecylenic acid, lanolinic acid, and isostearic acid.

[0133] Examples of oils and fats that may be contained in the present cosmetic or quasi-drug include coconut oil, palm oil, hydrogenated palm oil, avocado oil, sesame oil, olive oil, kukui nut oil, grape kernel oil, safflower oil, almond oil, corn oil, cottonseed oil, sunflower seed oil, grape seed oil, hazelnut oil, macadamia nut oil, meadowfoam oil, and rosehip oil.

[0134] Examples of ester oils that may be contained in the present cosmetic or quasi-drug include ethyl oleate, isopropyl myristate, isopropyl palmitate, myristyl myristate, cetyl palmitate, oleyl oleate, octyldodecyl myristate, octyldodecyl oleate, ethyl isostearate, isopropyl isostearate, cetyl 2-ethylhexanoate, cetostearyl 2-ethylhexanoate, glyceryl tri-2-ethylhexanoate, caprylic / capric triglyceride, glyceryl triisopalmitate, pentaerythritol tetra-2-ethylhexanoate, isocetyl octanoate, isostearyl octanoate, isocetyl isostearate, octyldodecyl isostearate, and octyldodecyl dimethyloctanoate.

[0135] Examples of silicone oils that may be contained in the present cosmetic or quasi-drug include methylpolysiloxane, highly polymerized methylpolysiloxane, methylphenylpolysiloxane, octamethyltrisiloxane, decamethyltetrasiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, methylcyclopolysiloxane, alcohol-modified silicone, alkyl-modified silicone, amino-modified silicone, and epoxy-modified silicone.

[0136] Examples of hydrocarbon oils that may be contained in the present cosmetic or quasi-drug include liquid paraffin, olive squalane, rice squalane, squalane, pristane, white petrolatum, paraffin wax, ozokerite, ceresin, and microcrystalline wax.

[0137] Examples of moisturizing agents that may be contained in the present cosmetic or quasi-drug include glycerin, 1,3-butylene glycol, chondroitin sulfate, hyaluronic acid, mucoitin sulfate, caronic acid, atelocollagen, cholesteryl-12-hydroxystearate, sodium lactate, bile salts, dl-pyrrolidone carboxylate, short-chain soluble collagen, diglycerin (EO)PO adduct, Rosa rugosa extract, Achillea millefolium extract, and Melilot extract.

[0138] Examples of water-soluble polymers that may be contained in the present cosmetic or quasi-drug include plant-based polymers (e.g., gum arabic, tragacanth gum, galactan, guar gum, carob gum, karaya gum, carrageenan, pectin, agar, quince seed, algae colloid (cassow extract), starch (rice, corn, potato, wheat), glycyrrhizic acid); microbial-based polymers (e.g., xanthan gum, dextran, succinoglucan, pullulan, etc.); animal-based polymers (e.g., collagen, casein, albumin, gelatin, etc.); starch-based polymers (e.g., carboxymethyl starch, methylhydroxypropyl starch, etc.); cellulose-based polymers (methylcellulose, ethylcellulose, methylhydroxypropylcellulose, Examples of suitable polymers include hydroxyethyl cellulose, sodium cellulose sulfate, hydroxypropyl cellulose, carboxymethyl cellulose, sodium carboxymethyl cellulose, crystalline cellulose, cellulose powder, etc.; alginic acid polymers (e.g., sodium alginate, propylene glycol alginate, etc.); vinyl polymers (e.g., polyvinyl alcohol, polyvinyl methyl ether, polyvinylpyrrolidone, carboxyvinyl polymer (carbomer), etc.); polyoxyethylene polymers (e.g., polyethylene glycol 20,000, 40,000, 60,000, etc.); acrylic polymers (e.g., sodium polyacrylate, polyethyl acrylate, polyacrylamide, etc.); polyethyleneimine; cationic polymers; and the like.

[0139] The content of the water-soluble polymer contained in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.001 parts by mass or more, more preferably 0.005 parts by mass or more, even more preferably 0.05 parts by mass or more, and preferably 3 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.5 parts by mass or less. The content of the water-soluble polymer contained in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.001 to 3 parts by mass, more preferably 0.005 to 1 part by mass, and even more preferably 0.05 to 0.5 parts by mass.

[0140] Examples of antioxidants that may be contained in the present cosmetic or quasi-drug include tocopherols, dibutylhydroxytoluene, butylhydroxyanisole, and gallic acid esters.

[0141] Examples of ultraviolet absorbents that may be contained in the present cosmetic or quasi-drug include benzoic acid-based ultraviolet absorbents (e.g., para-aminobenzoic acid (hereinafter abbreviated as PABA), PABA monoglycerin ester, N,N-dipropoxy PABA ethyl ester, N,N-diethoxy PABA ethyl ester, N,N-dimethyl PABA ethyl ester, N,N-dimethyl PABA butyl ester, N,N-dimethyl PABA ethyl ester, etc.); anthranilic acid-based ultraviolet absorbents (e.g., homomenthyl-N-acetylanthranilate, etc.); and salicylic acid-based ultraviolet absorbents. (e.g., amyl salicylate, menthyl salicylate, homomenthyl salicylate, octyl salicylate, phenyl salicylate, benzyl salicylate, p-isopropanol phenyl salicylate, etc.); cinnamic acid-based ultraviolet absorbers (e.g., octyl cinnamate, ethyl-4-isopropyl cinnamate, methyl-2,5-diisopropyl cinnamate, ethyl-2,4-diisopropyl cinnamate, methyl-2,4-diisopropyl cinnamate, propyl-p-methoxy cinnamate, isopropyl-p-methoxy cinnamate, isopropyl Amyl-p-methoxycinnamate, octyl-p-methoxycinnamate (2-ethylhexyl-p-methoxycinnamate), 2-ethoxyethyl-p-methoxycinnamate, cyclohexyl-p-methoxycinnamate, ethyl-α-cyano-β-phenylcinnamate, 2-ethylhexyl-α-cyano-β-phenylcinnamate, glyceryl mono-2-ethylhexanoyl-di-paramethoxycinnamate, etc.; benzophenone-based ultraviolet absorbers (e.g., 2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4-methoxy Benzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-4'-methylbenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonate, 4-phenylbenzophenone, 2-ethylhexyl-4'-phenyl-benzophenone-2-carboxylate, 2-hydroxy-4-n-octoxybenzophenone, 4-hydroxy-3-carboxybenzophenone, etc.);3-(4'-methylbenzylidene)-d,L-camphor, 3-benzylidene-d,l-camphor; 2-phenyl-5-methylbenzoxazole; 2,2'-hydroxy-5-methylphenylbenzotriazole; 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole; 2-(2'-hydroxy-5'-methylphenylbenzotriazole; dibenzalazine; dianisoylmethane; 4-methoxy-4'-t-butyldibenzoylmethane; 5-(3,3-dimethyl-2-norbornylidene)-3-pentan-2-one; and the like.

[0142] Examples of chelating agents that may be contained in the present cosmetic or quasi-drug include 1-hydroxyethane-1,1-diphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid tetrasodium salt, disodium edetate, trisodium edetate, tetrasodium edetate, sodium citrate, sodium polyphosphate, sodium metaphosphate, gluconic acid, phosphoric acid, citric acid, ascorbic acid, succinic acid, edetic acid, and trisodium ethylenediaminehydroxyethyltriacetate.

[0143] Examples of preservatives and antibacterial agents that may be contained in the present cosmetic or quasi-drug include parabens such as ethylparaben, isopropylparaben, butylparaben, and benzylparaben, and their sodium salts, benzoic acid, benzoate salts, alkyldiaminoethylglycine hydrochloride, photosensitizers, chlorcresol, chlorobutanol, salicylic acid, salicylates, sorbic acid and its salts, dehydroacetic acid and its salts, trichlorohydroxydiphenyl ether (also known as triclosan), phenoxyethanol, phenol, sodium lauryldiaminoethylglycine, resorcinol, and nitrocellulose. Examples include lead-ammonia-silver complex substituted zeolite, pantothenyl ethyl ether benzoate, isopropyl methylphenol, cetylpyridinium chloride, benzalkonium chloride, benzethonium chloride, chlorhexidine hydrochloride, orthophenylphenol, sodium orthophenylphenol, silver-copper zeolite, chlorhexidine gluconate, cresol, chloramine T, chloroxylenol, chlorphenesin, chlorhexidine, 1,3-dimethylol-5,5-dimethylhydantoin, alkylisoquinolinium bromide, thianthol, and thymol.

[0144] The content of the preservative and / or antibacterial agent contained in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, even more preferably 0.05 parts by mass or more, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 1 part by mass or less. The content of the preservative and / or antibacterial agent contained in 100 parts by mass of the present cosmetic or quasi-drug is preferably 0.001 to 5 parts by mass, more preferably 0.001 to 3 parts by mass, and even more preferably 0.05 to 1 part by mass.

[0145] Examples of fragrances that may be contained in the present cosmetic or quasi-drug include terpenes and terpenoids such as citral, menthol, camphor, salvinorin A, cannabinoids, hinokitiol, limonene, farnesol, and vitamin A; aromatic alcohols such as phenoxyethanol, phenols such as eugenol and shogaol; esters such as butyric acid esters and propionic acid esters; lactones such as γ-nonalactone and γ-undecalactone; and aldehydes having 6 to 20 carbon atoms. In this specification, components that can be classified as both polyhydric alcohols and fragrances are classified as fragrances. EXAMPLES

[0146] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0147] Manufacturing Example [Production Example 1] A reaction solution was prepared by dissolving 4.79 g of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) as an internal crosslinking agent in 5,500 g of a 33 wt % aqueous solution of sodium acrylate with a neutralization rate of 75 mol %. Next, this reaction solution was degassed for 30 minutes under a nitrogen gas atmosphere (specifically, nitrogen gas was blown into the reaction solution for 30 minutes to expel dissolved oxygen in the reaction solution). Next, the degassed reaction solution was supplied to a reactor prepared by attaching a lid to a jacketed stainless steel double-arm kneader with an internal volume of 10 L and two sigma-type blades, and the system was substituted with nitrogen gas while maintaining the reaction solution at 25°C. Next, 2.4 g of ammonium persulfate and 0.12 g of L-ascorbic acid were added as polymerization initiators while stirring the reaction solution. The polymerization reaction started about 1 minute after the addition of the polymerization initiator. The polymerization reaction was continued at a temperature of 25 to 90° C. (peak temperature), and 40 minutes after the start of the polymerization, the reaction was terminated and a hydrous gel-like crosslinked polymer was taken out.

[0148] The obtained hydrogel crosslinked polymer was fragmented to a diameter of about 5 mm. This fragmented hydrogel crosslinked polymer (particulate hydrogel) was spread on a 50 mesh wire net (opening size 300 μm) and dried with hot air at 170° C. for 70 minutes to obtain a dried polymer.

[0149] Next, the obtained dried polymer was pulverized using a vibration mill, and then classified using a JIS standard sieve with an opening of 850 μm to obtain a sieve-passing material. Through this series of operations, a pulverized intermediate (1) was obtained.

[0150] [Production Example 2] 100 parts by weight of the pulverized intermediate (1) obtained in Production Example 1 was mixed with an aqueous surface cross-linking agent solution consisting of 0.7 parts by weight of propylene glycol, 0.02 parts by weight of ethylene glycol diglycidyl ether, 2 parts by weight of water, and 0.7 parts by weight of ethyl alcohol. The mixture was heated at 185°C for 40 minutes to obtain a surface-cross-linked pulverized intermediate (1). Next, 0.3 g of hydrophilic silicon dioxide (trade name: Aerosil 200 (average particle size of primary particles: approximately 12 nm); manufactured by Nippon Aerosil Co., Ltd.) was added as an inorganic powder to 100 g of the surface-cross-linked pulverized intermediate (1) and mixed (dry blended) to obtain a pulverized intermediate (2).

[0151] [Production Example 3] 7.5 g of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) was dissolved as an internal crosslinking agent in 5,500 g of an aqueous solution of sodium acrylate having a neutralization rate of 75 mol% (monomer concentration: 38% by mass) to obtain a reaction solution. Next, the reaction solution was supplied to a reactor prepared by attaching a lid to a jacketed stainless steel double-arm kneader having an internal volume of 10 L and two sigma-type blades, and the system was replaced with nitrogen gas while the reaction solution was kept at 30°C to remove dissolved oxygen. Next, 29.8 g of a 10% by mass aqueous solution of sodium persulfate and 1.5 g of a 1% by mass aqueous solution of L-ascorbic acid were added as polymerization initiators while stirring the reaction solution. The polymerization reaction started about 1 minute after the addition of the polymerization initiator. The polymerization peak temperature was 86°C 17 minutes after the start of polymerization, and the reaction was stopped 60 minutes after the start of polymerization, and the hydrogel-like crosslinked polymer was taken out. The obtained hydrogel-like crosslinked polymer was finely divided into particles of about 1 to 4 mm.

[0152] This finely divided hydrogel crosslinked polymer (particulate hydrogel) was spread on a 50 mesh (mesh size: 300 μm) wire net and dried with hot air at 160° C. for 60 minutes to obtain a dried polymer. The resulting dried polymer was then pulverized using a roll mill and further classified using a JIS standard sieve with a mesh size of 450 μm. Particles with a size of 450 μm or more were pulverized again using a roll mill and classified using a JIS standard sieve with a mesh size of 450 μm, and the particles that passed through the two types of sieves were combined. Through this series of operations, a pulverized intermediate (3) was obtained.

[0153] [Production Example 4] 100 parts by mass of the ground intermediate (3) obtained in Production Example 3 was mixed with 0.7 parts by mass of an aqueous surface cross-linking agent solution consisting of 0.1 parts by mass of ethylene glycol diglycidyl ether, 0.3 parts by mass of propylene glycol, and 0.3 parts by mass of water. The mixture was heat-treated for 20 minutes in a mortar mixer heated to 210°C to obtain a surface-cross-linked ground intermediate (3). 100 parts by mass of the obtained surface-cross-linked ground intermediate (3) was spray-mixed with a mixed solution consisting of 0.01 parts by mass of sodium diethylenetriamine pentaacetate, 0.1 parts by mass of a 15% aqueous solution of a leaf extract of a plant of the family Theaceae (product name: FS-80MO, sold by Shirai Matsu Shinyaku Co., Ltd. (location: 37-1 Ukawa, Minakuchi-cho, Koka-gun, Shiga Prefecture)), and 3 parts by mass of water. The obtained mixture was heated and cured at 60°C for 1 hour while maintaining a water content of 3% by mass, and passed through a wire mesh with an opening of 600 μm. To 100 parts by mass of the obtained polymer composition, 0.3 parts by mass of fine particle silicon dioxide (product name: Aerosil 200) as an inorganic powder was added and mixed (dry blended) to obtain a pulverized intermediate (4).

[0154] [Production Example 5] In a 2-liter polypropylene container, 421.7 g of acrylic acid, 2.4 g of polyethylene glycol diacrylate (average number of moles of ethylene oxide added: 9) as an internal crosslinking agent, 11.3 g of 1.0 wt% aqueous solution of trisodium diethylenetriaminepentaacetate, 140.4 g of 48.5 wt% aqueous solution of sodium hydroxide, 4.4 g of 1.0 wt% aqueous solution of polyoxyethylene (20) sorbitan monostearate (manufactured by Kao Corporation), and 390.3 g of deionized water (ion-exchanged water) were added and mixed to prepare an aqueous solution of monomer (a'). The temperature of the aqueous solution of monomer (a') rose to 62.9°C due to the heat of neutralization in the first stage immediately after preparation. Next, the aqueous solution of monomer (a') was cooled while stirring. When the liquid temperature reached 38°C, 211.9g of 48.5wt% sodium hydroxide aqueous solution adjusted to 40°C was added to the monomer aqueous solution (a') and mixed to prepare the monomer aqueous solution (a). At this time, the temperature of the monomer aqueous solution (a) rose to 81.7°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5wt% sodium hydroxide aqueous solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution. Next, nitrogen gas was introduced into the monomer aqueous solution (a) at 0.1L / min for 5 seconds using a Kinoshita glass bowl filter (filter particle No. 4 / Kinoshita Rika Kogyo Co., Ltd.). Next, 17.6g of 4.0wt% sodium persulfate aqueous solution was added to the monomer aqueous solution (a) in a stirred state, and then immediately poured into a stainless steel bat-type container (bottom 340×340mm, height 25mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The time from the start of the second neutralization to pouring the aqueous monomer solution (a) into the vat-shaped container was 55 seconds, and the vat-shaped container was heated using a hot plate (NEOHOTPLATE HI-1000 / Iuchi Seiei-do Co., Ltd.) until the surface temperature reached 40°C. The polymerization reaction started 60 seconds after the aqueous monomer solution (a) was poured into the vat-shaped container. The polymerization reaction proceeded with the reactants expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than that of the vat-shaped container. Three minutes after the start of the polymerization reaction, a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") was taken out as the reactant.The series of operations was carried out in an open atmosphere. The peak temperature during polymerization was 108°C.

[0155] The hydrogel obtained by the polymerization reaction was crushed using a meat chopper (HL-3225N, plate hole diameter: 8.0 mm / Remacom Co., Ltd.) to obtain a particulate hydrogel. The amount of the hydrogel fed to the meat chopper was 230 g / min, and deionized water adjusted to 90° C. was added at 50 g / min in parallel with the feeding of the hydrogel to perform gel crushing. The obtained particulate hydrogel was spread and placed on a stainless steel wire mesh with an opening of 850 μm, and dried by ventilating hot air at 180° C. for 30 minutes to obtain a dried polymer. Next, the dried polymer obtained by the drying operation was crushed using a roll mill (WL type roll crusher / Inokuchi Giken Co., Ltd.), and then classified using a JIS standard sieve with an opening of 710 μm to obtain a sieve-passing material. Through this series of operations, a crushed intermediate (5) was obtained.

[0156] [Production Example 6] A surface crosslinking agent solution consisting of 0.3 parts by weight of ethylene carbonate, 0.6 parts by weight of propylene glycol, 3.0 parts by weight of deionized water (ion-exchanged water), and 0.001 parts by weight of polyoxyethylene (20) sorbitan monostearate (Kao Corporation) (10 ppm relative to the ground intermediate (5)) was added to 100 parts by weight of the ground intermediate (5) obtained in Production Example 5 and mixed uniformly. Thereafter, the mixture was heated at 208°C for 40 minutes to perform surface crosslinking.

[0157] After the heat treatment, the surface cross-linked pulverized intermediate (5) obtained was pulverized until it passed through a JIS standard sieve with an opening of 850 μm, to obtain a pulverized intermediate (6).

[0158] [Production Example 7] A reaction solution was prepared by dissolving 2.83 g of trimethylolpropane triacrylate as an internal crosslinking agent in 5,500 g of a 33 wt % aqueous solution of sodium acrylate with a neutralization rate of 75 mol %. Next, this reaction solution was degassed for 30 minutes under a nitrogen gas atmosphere (specifically, nitrogen gas was blown into the reaction solution for 30 minutes to expel dissolved oxygen in the reaction solution). Next, the degassed reaction solution was supplied to a reactor prepared by attaching a lid to a jacketed stainless steel double-arm kneader with an internal volume of 10 L having two sigma-type blades, and the system was substituted with nitrogen gas while maintaining the reaction solution at 25°C. Next, 2.4 g of ammonium persulfate and 0.12 g of L-ascorbic acid were added as polymerization initiators while stirring the reaction solution. The polymerization reaction started about 1 minute after the addition of the polymerization initiator. The polymerization reaction was continued at a temperature of 25 to 90°C (peak temperature), and the reaction was terminated 40 minutes after the start of polymerization, and a hydrogel-like crosslinked polymer was taken out.

[0159] The obtained hydrogel crosslinked polymer was fragmented to a diameter of about 5 mm. This fragmented hydrogel crosslinked polymer (particulate hydrogel) was spread on a 50 mesh wire net (opening size 300 μm) and dried with hot air at 170° C. for 70 minutes to obtain a dried polymer.

[0160] Next, the obtained dried polymer was pulverized using a vibration mill, and then classified using a JIS standard sieve with an opening of 850 μm to obtain a sieve-passing material. Through this series of operations, a pulverized intermediate (7) was obtained.

[0161] [Production Example 8] A surface crosslinking agent aqueous solution consisting of 0.7 parts by weight of propylene glycol, 0.02 parts by weight of ethylene glycol diglycidyl ether, 2 parts by weight of water, and 0.7 parts by weight of ethyl alcohol was mixed with 100 parts by weight of the pulverized intermediate (7) obtained in Production Example 7. The mixture was heat-treated at 185°C for 40 minutes to obtain a pulverized intermediate (8).

[0162] [Examples 1 to 8] The respective pulverized intermediates (1) to (8) were pulverized in the combinations shown in Tables 1 and 2 below by any of the pulverization methods shown in Pulverization Examples 1 to 4 below to obtain finely pulverized crosslinked polymer particles 1 to 8. The physical properties of the obtained crosslinked polymer particles 1 to 8 were measured and evaluated. The results are shown in Table 3. The obtained crosslinked polymer particles 1 to 8 were all irregularly pulverized particles (proportion of irregularly pulverized particles=100%).

[0163] [Crushing Example 1] The intermediate product was finely pulverized using a supersonic jet mill LJ-3 (manufactured by Nippon Pneumatic Mfg. Co., Ltd.) at a pulverization pressure of 0.6 MPa.

[0164] [Crushing Example 2] The intermediate product was finely pulverized using a Super Jet Mill SJ-500 (manufactured by Nisshin Engineering Co., Ltd.) at a pulverization pressure of 0.6 MPa.

[0165] [Crushing Example 3] The intermediate product was finely ground using a Silphid Mill SIW-10 (Dalton). [Crushing Example 4] 400 g of the intermediate ground material and 3 kg of 10 mm SUS balls were placed in a SUS pot mill (volume 3 L) and processed at 30 rpm for 24 hours to finely grind the material.

[0166] [Table 1]

[0167] [Table 2]

[0168] [Example 9] Purified water was added to the crosslinked polymer particles 8 to prepare a 1% by mass aqueous solution of the crosslinked polymer particles 8. This aqueous solution was filtered under reduced pressure using a 0.22 μm filter, and washed three times with purified water in an amount twice that of the aqueous solution before filtration. The crosslinked polymer particles after washing were freeze-dried to obtain crosslinked polymer particles 9. The physical properties of the obtained crosslinked polymer particles 9 were measured and evaluated. The results are shown in Table 3.

[0169] [Example 10] Purified water was added to the crosslinked polymer particles 8 to prepare a 1% by mass aqueous solution of the crosslinked polymer particles 8. Acrylic acid was added to this 1% aqueous solution to a concentration of 550 ppm relative to 100 parts by mass of the crosslinked polymer particles, and the mixture was stirred and mixed for 30 minutes or more using a propeller. The crosslinked polymer particles after stirring and mixing were freeze-dried to obtain crosslinked polymer particles 10. The physical properties of the obtained crosslinked polymer particles 10 were measured and evaluated. The results are shown in Table 3.

[0170] [Comparative Example 1] Purified water was added to the crosslinked polymer particles 9 obtained in Example 9 to prepare a 1% by mass aqueous solution of the crosslinked polymer particles 9. Acrylic acid was added to this 1% aqueous solution so that the concentration was 1230 ppm relative to 100 parts by mass of the crosslinked polymer particles, and the mixture was stirred and mixed for 30 minutes or more using a propeller. The crosslinked polymer particles after stirring and mixing were freeze-dried to obtain comparative crosslinked polymer particles 1. The physical properties of the obtained comparative crosslinked polymer particles 1 were measured and evaluated. The results are shown in Table 3.

[0171] [Comparative Example 2] The crosslinked polymer particles 9 and the crosslinked polymer particles 8 obtained in Example 9 were placed in a container in a ratio of 7:3. The crosslinked polymer particles in the container were mixed for 10 minutes using a paint shaker. Purified water was added to the mixed particles to prepare a 1% by mass aqueous solution of the mixed particles. Acrylic acid was added thereto so as to have a concentration of 1250 ppm relative to 100 parts by mass of the crosslinked polymer particles, and the mixture was stirred and mixed for 30 minutes or more using a propeller. The crosslinked polymer particles after stirring and mixing were freeze-dried to obtain comparative crosslinked polymer particles 2. The obtained comparative crosslinked polymer particles 2 were measured and evaluated for each physical property. The results are shown in Table 3.

[0172] [Comparative Example 3] A reaction vessel was charged with 99.9 parts of acrylic acid, 0.1 parts of polyethylene glycol #600 diacrylate [A-400 manufactured by Shin-Nakamura Chemical Co., Ltd.], and 400 parts of water, and the liquid temperature was adjusted to 10° C. under a nitrogen atmosphere.

[0173] Next, a mixed solution of 1 part by mass of 1% hydrogen peroxide water and 1 part by mass of 0.5% aqueous ascorbic acid solution was added to the reaction system to initiate polymerization. Six hours after the start of polymerization, the gel-like hydrated crosslinked polymer formed was taken out. The peak temperature during polymerization was 67°C.

[0174] 500 parts by mass of this gel-like hydrous crosslinked polymer was chopped, and then neutralized (75 mol %) by adding 73.5 parts of a 50% aqueous sodium hydroxide solution.

[0175] The neutralized gel-like hydrous cross-linked polymer was dried in a drum dryer heated to 160° C., and then pulverized to a volume average particle size of 30 μm to obtain comparative cross-linked polymer particles 3. The obtained comparative cross-linked polymer particles 3 were measured and evaluated for each physical property. The results are shown in Table 3.

[0176] [Table 3]

[0177] [Table 4]

[0178] 〔summary〕 Table 3 shows the measurement and evaluation results of each physical property of the crosslinked polymer particles obtained in the examples and comparative examples. From Table 3, it can be seen that the crosslinked polymer particles of Examples 1 to 10, which have a specific volume average particle size and a residual monomer amount of 1000 ppm or less, can impart excellent thickness when applied to the skin, etc. In addition, it can be seen that the crosslinked polymer particles of Examples 1 to 8 and 10 are also excellent in spreadability, fluffy feeling, and emulsion stability when applied. It can also be seen that the crosslinked polymer particles of Examples 1, 3, 4, and 7 are also excellent in water absorption capacity.

[0179] On the other hand, the crosslinked polymer particles of Comparative Examples 1 to 3 in which the amount of residual monomer exceeds 1000 ppm do not have a sufficient thickness when applied, and are also insufficient in terms of spreadability when applied, fluffy feeling, and emulsion stability.

[0180] [Measurement method] [Method of measuring volume average particle size and half width] The volume average particle diameter (D50) of the crosslinked polymer particles was measured using a laser diffraction scattering type particle size distribution analyzer LA-950 manufactured by HORIBA. Ethyl acetate was used as the circulating solvent during the measurement, and the refractive index of the dispersion was set to 1.59, and that of the dispersion medium was set to 1.371. The median diameter (μm) was calculated from the particle size distribution on a volume basis obtained by the measurement, and was taken as the volume average particle diameter (D50) of the crosslinked polymer particles.

[0181] The half-value width of the crosslinked polymer particles was calculated based on the particle size distribution graph obtained by the volume average particle size measurement. Specifically, the half-value of the frequency was calculated from the maximum frequency value, the particle size at the half-value was calculated from the approximate curve of the region including the half-value, and the difference between the particle sizes at the two points was taken as the half-value width.

[0182] [Method for measuring residual monomer amount] The amount of residual monomer in the crosslinked polymer particles was measured according to the EDANA method (WSP210.3(10)). Specifically, 1.0 g of the crosslinked polymer particles was added to 200 ml of 0.9% by mass sodium chloride aqueous solution while stirring, and dispersed for 1 hour. The filtrate was then analyzed by HPLC to measure the amount of residual monomer (unit: ppm by mass).

[0183] [Method of measuring viscosity] The method for measuring the viscosity of the crosslinked polymer particles was as follows: For each crosslinked polymer particle, a blend was prepared by blending purified water so that the concentration of the crosslinked polymer particles was 1% by mass. The viscosity of the blend was measured using a Toki Sangyo Co., Ltd. B-type viscometer TVB-10 at a rotor TM4, a rotation speed of 1.5 rpm or 6 rpm, a measurement time of 60 seconds, and a temperature of 25°C. The measured viscosity was regarded as the viscosity of the crosslinked polymer particles.

[0184] [Soluble content] The method for measuring the soluble content of the crosslinked polymer particles was as follows: (1) First, as a pretreatment for the measurement, the crosslinked polymer particles were dried at 80°C for 3 hours in a vacuum dryer with the pressure reduced to 5 kPa; (2) 500 g of 0.9% by mass NaCl aqueous solution and a stirrer (8 mmφ×30 mm without ring) were placed in a 500 mL beaker and adjusted to rotate at 600 rpm; (3) 2.0 g of the crosslinked polymer particles were placed in the beaker over 1 minute and stirred at 25°C for 3 hours; (4) After stirring, the mixture was filtered. The stirred liquid was filtered using paper (ADVANTEC, No. 2); (5) 80 g of the obtained filtrate was weighed into a 100 mL beaker previously weighed at 140°C and dried for 16 hours in a hot air dryer (Espec Corp., PHH102) at 140°C, and the mass of the filtrate solids, Wa (g), was measured; (6) The above operations (2) to (5) were carried out in the same manner without using the crosslinked polymer particles, and the mass of the filtrate solids, Wb (g), was measured; (7) The soluble content of the crosslinked polymer particles was calculated by the following formula: Soluble fraction of crosslinked polymer particles (% by mass)=[((Wa−Wb) / 80)×500 / 2]×100.

[0185] [Sensory evaluation] The sensory evaluation method was as follows. A 1% by mass aqueous solution of each of the obtained crosslinked polymer particles was prepared, and sensory evaluation was performed by a specialist panelist when the solution was applied to the inside of the forearm. The evaluation items were thickness when applied, spread when applied, and plumpness, and each item was scored on a 5-point scale, and the average value (rounded up) was used as the overall evaluation. The specific evaluation criteria for each evaluation item were as follows.

[0186] <Sensory evaluation criteria> (Thickness when applied) 5: Very thick 4: Thick 3: Slightly thick 2: Slightly thin 1: No thickness (Spread when applied) 5: Very stretchy 4: Good stretch 3: Slightly stretchy 2: Slightly poor stretch 1: Poor stretch (Fluffy feeling) 5: It feels very fluffy 4: It has a plump feel 3: Slightly plump to the touch 2: Not very plump 1: It doesn't feel plump.

[0187] [Emulsification stability] The emulsion stability of the crosslinked polymer particles was evaluated as follows. 10 g of cetyl ethylhexanoate and 90 g of a 1% by mass aqueous solution of each crosslinked polymer particle were mixed and stirred at 2000 rpm using a disper, and the appearance was observed after storing at room temperature for one week. Based on the observation results, the emulsion stability of the crosslinked polymer particles was evaluated according to the following criteria.

[0188] <Emulsion stability evaluation criteria> 5: The particles are fine in appearance and there is almost no oil separation. 4: Fine particles in appearance, with very little oil separation 3: The emulsion particles appear large, and there is slight oil separation. 2: The emulsion particles appear large and oil separates. 1: The emulsion particles appear large and there is considerable oil separation.

[0189] Aspect Ratio The aspect ratio of the crosslinked polymer particles was calculated using the image processing software "Image J".

[0190] [Water absorption rate] The method for measuring the water absorption ratio of the crosslinked polymer particles was as follows. First, an excess amount of purified water (100 ml) at 25°C was added to 0.2 g of the crosslinked polymer particles, and the mixture was stirred at 500 rpm using a propeller (four blades with a diameter of 7 cm), and stirred for 30 minutes or more after the mixture had disappeared. Thereafter, the dispersion containing the swollen (water-absorbed) crosslinked polymer particles was filtered under reduced pressure at 4.5 kpa using a 0.22 μm filter, and the weight was measured and used as the weight at the time of water absorption. After the measurement, the collected dispersion was heated and dried at 150°C for 60 minutes, and the weight of the residue was measured and used as the dry weight. The water absorption ratio of the crosslinked polymer particles was calculated based on the following formula. Water absorption capacity of crosslinked polymer particles = [weight when absorbed (g) - dry weight (g)] / dry weight (g). [Formulation example] [Lotion] Using the obtained crosslinked polymer particles 1, a lotion having the formulation shown in Table 5 below was prepared.

[0191] (Preparation method) After mixing components 2 to 4, component 1 was added and dispersed for 1 minute at 500 rpm using a three-one motor. Then, components 5 and 6 were added in order and dispersed for 2 minutes at 500 rpm using a three-one motor, and finally component 7 was added and dispersed for 15 minutes at 500 rpm using a three-one motor to obtain a lotion. This lotion was able to impart excellent thickness when applied and had excellent moisturizing power and long-lasting effect.

[0192] [Table 5]

[0193] [Gel] Using the obtained crosslinked polymer particles 2, a gel having the formulation shown in Table 6 below was prepared.

[0194] (Preparation method) Component 2 was added to component 1 and dispersed for 30 minutes at 700 rpm using a three-one motor. Components 3 to 5 were uniformly dispersed and added to the mixture of components 1 and 2, and then mixed by hand stirring. After thoroughly and uniformly mixing, components 6 and 7 were added in sequence and mixed uniformly by hand stirring to obtain a gel. This gel was able to impart excellent thickness when applied and had excellent moisturizing power and durability.

[0195] [Table 6]

[0196] [Emulsion] Using the obtained crosslinked polymer particles 3, an emulsion having the formulation shown in Table 7 below was prepared.

[0197] (Preparation method) Component 15 in Table 7 was added to a portion of component 16 and stirred to form a viscous liquid (part A). Next, components 1 to 8 were heated to about 70°C and dissolved (part B). Components 9 to 14 and the remaining component 16 were heated to about 70°C and dissolved (part C). Part C was added to part B with stirring to emulsify, then cooled to about 50°C, part A was added and stirred until uniform, yielding an emulsion. This emulsion was able to impart excellent thickness when applied and was excellent in the effect of imparting a moist feeling.

[0198] [Table 7]

[0199] [Beauty serum] Using the obtained crosslinked polymer particles 8, a beauty essence having the formulation shown in Table 8 below was prepared.

[0200] (Manufacturing method) First, the components listed in Table 8 were mixed uniformly for each section to obtain a mixture (Parts A to C). Parts A and C were dissolved at 80°C. Part B was gradually added to Part A while stirring and mixed, then Part C was added and stirred to make uniform, and the mixture was cooled to obtain a beauty essence. This beauty essence was able to impart excellent thickness when applied, and also had a high moisturizing effect, softened the skin, and maintained a fresh, smooth, moisturized skin for a long time.

[0201] [Table 8]

[0202] [Introducing serum] Using the obtained crosslinked polymer particles 4, an introduction beauty essence having the formulation shown in Table 9 below was prepared.

[0203] (Manufacturing method) The components listed in Table 9 were mixed uniformly for each section to obtain a mixture (Parts A and C). Part B was gradually added to Part A while stirring and mixed, and then Parts C to H were added in order and stirred until uniform, obtaining an introduction serum. This introduction serum was able to impart excellent thickness when applied, and had a high penetration and moisturizing effect, softening the skin and keeping the skin fresh, smooth, and moisturized for a long time.

[0204] [Table 9]

[0205] [Massage cream] Using the obtained crosslinked polymer particles 5, a massage cream having the formulation shown in Table 10 below was prepared.

[0206] (Preparation method) Components 1 to 17 in Table 10 were heated to about 70°C and uniformly dissolved (Part A). Next, components 18 to 22 were heated to about 70°C and uniformly dissolved (Part B). Part B was added to Part A with stirring, emulsified, and then cooled to obtain a massage cream. This massage cream was a cream that could impart excellent thickness when applied, had a high massage effect, and was excellent in the effect of imparting a moist feeling.

[0207] [Table 10]

[0208] [Emollient cream] Using the obtained crosslinked polymer particles 6, an emollient cream having the formulation shown in Table 11 below was prepared.

[0209] (Preparation method) Components 1 to 10 in Table 11 were added and heated to about 80°C to dissolve (Part A). Components 11 to 15 were placed in a separate container and heated to about 80°C to dissolve uniformly (Part B). Part B was added to Part A and emulsified using a homomixer, then cooled to 40°C to obtain an emollient cream. This emollient cream was a cream that could impart excellent thickness when applied and had an excellent effect of imparting a moist feeling.

[0210] [Table 11]

[0211] [Anti-aging cream] Using the obtained crosslinked polymer particles 7, an anti-aging cream having the formulation shown in Table 12 below was prepared.

[0212] (Manufacturing method) Each component of section A was heated to about 80°C and dissolved uniformly (part A). Each component of section B was heated to about 80°C and dissolved uniformly (part B). While stirring with a homomixer at about 80°C, part B was gradually added to part A, and after emulsification, the mixture was mixed uniformly and cooled to about 30°C to obtain an anti-aging cream. This anti-aging cream was a cream that could impart excellent thickness when applied, had good spreadability, and was excellent in the effect of imparting a moist feeling.

[0213] [Table 12]

[0214] [Base cream] Using the obtained crosslinked polymer particles 1, a base cream having the formulation shown in Table 13 below was prepared.

[0215] (Preparation method) The components listed in Table 13 were mixed uniformly for each section to obtain a mixture (Parts A to C). Part A was heated to 80°C, and Part B was added and mixed. Part C was added to the obtained mixture and emulsified, and then mixed uniformly. After stirring, the mixture was cooled to 40°C to obtain a base cream. This base cream spreads well, has good foundation adhesion and staying power, and can impart a smooth feel.

[0216] [Table 13] [Industrial Applicability]

[0217] The crosslinked polymer particles according to one embodiment of the present invention can be suitably used in the fields of cosmetics and quasi-drugs.

Claims

1. A crosslinked polymer particle for use in a cosmetic or quasi-drug, comprising: The crosslinked polymer particles have a content of structural units derived from (meth)acrylic acid (salt) of 20 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the crosslinked polymer, A crosslinked polymer particle for use in cosmetics or quasi-drugs, having a residual monomer amount of 1000 ppm or less.

2. 2. The crosslinked polymer particles for use in cosmetics or quasi-drugs according to claim 1, having a soluble content of 15% by mass or more.

3. 2. The crosslinked polymer particles for use in cosmetics or quasi-drugs according to claim 1, having a volume average particle size of 8 μm or more and 20 μm or less.

4. 2. The crosslinked polymer particle for use in cosmetics or quasi-drugs according to claim 1, wherein the crosslinked polymer is crosslinked with a compound having two or more ethylenically unsaturated groups in one molecule.

5. The content of structural units derived from a (meth)acrylate salt per 100 parts by mass of the crosslinked polymer is 20 parts by mass or more, and 2. The crosslinked polymer particles for use in cosmetics or quasi-drugs according to claim 1, wherein the (meth)acrylate salt is a salt of (meth)acrylic acid and a monovalent metal.

6. A composition comprising the crosslinked polymer particles according to any one of claims 1 to 5 and an oil agent.

7. A cosmetic or quasi-drug comprising the crosslinked polymer particles according to any one of claims 1 to 5 or the composition according to claim 6.

8. The cosmetic or quasi-drug according to claim 7, which is for use on the skin.

Citation Information

Patent Citations

  • Cosmetic

    JP2019019058A